Organic el display device and method for manufacturing the same
Patent Information
- Application Number
- CN202280021295.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-26
- Filing Date
- 2022-03-22
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-03-22
AI Technical Summary
[0003]然而,这样的柔性的有机EL显示装置可能因弯曲、折叠这样的制造工序、使用方法而发生基板与有机EL层的剥离,结果,有机EL显示装置的可靠性会降低(例如,参见专利文献1)
[0017]就本发明的有机EL显示装置而言,能够通过简便的方法进行包括像素分割层和间隔件的形成的有机EL显示装置的制造,没有有机EL层的剥离,并且通过增加基板的扩散反射光而能够抑制外部光反射。
Smart Images

Figure CN116982407B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an organic EL display device having a plurality of display pixels arranged in a matrix and a method thereof. Background Technology
[0002] Organic EL (Organic Electron) displays are attracting attention as the next generation of flat panel displays. Organic EL refers to the electroluminescence of an organic EL layer formed by organic compounds and disposed between two electrodes. Furthermore, a display device utilizing organic EL light-emitting elements is called an organic EL display device. Self-emissive organic EL displays can achieve wide viewing angles, high-speed response, and high-contrast image display. By using substrates such as thin glass and plastic resins, they can be made thinner, lighter, and more flexible, thus their research and development have been vigorously promoted in recent years. Flexible organic EL displays are expected to be used in various fields, including flexible (bending without segmentation), rollable (rolling up), and foldable (folding).
[0003] However, such flexible organic EL display devices may experience peeling of the substrate from the organic EL layer due to manufacturing processes such as bending and folding, as well as usage methods, resulting in a decrease in the reliability of the organic EL display device (for example, see Patent Document 1).
[0004] On the other hand, if it is made into a mobile device, it is necessary to maintain display quality in various environments, whether indoors or outdoors. In particular, in the suppression of external light reflection, solutions such as combination with a circular polarizing plate and blackening of the substrate have been proposed (for example, see Patent Document 2).
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: Japanese Patent Application Publication No. 2020-87935
[0008] Patent Document 2: Japanese Patent Application Publication No. 2004-281365 Summary of the Invention
[0009] The problem that the invention aims to solve
[0010] However, for the organic EL display device described in Patent Document 1, which sets an inverted conical spacer on the pixel segmentation layer to suppress peeling caused by flexibility, it is difficult to set the material and manufacturing conditions due to the characteristics of the spacer shape. In addition, there are problems such as the inability to process the pixel segmentation layer and the spacer together, resulting in a decrease in panel yield and a significant increase in cost.
[0011] Furthermore, for the organic EL display device described in Patent Document 2, which blackens the first electrode and the pixel segmentation layer for the purpose of suppressing external light reflection, although it is expected that some external light reflection can be suppressed by coloring, the suppression of external light reflection is insufficient due to the smoothness of the reflective surface.
[0012] Therefore, the present invention aims to provide an organic EL display device and a method for manufacturing the same, which manufactures an organic EL display device including the formation of a pixel segmentation layer and spacers through a simple method, and as a flexible display device, has high reliability and can suppress external light reflection.
[0013] Methods for solving problems
[0014] The organic EL display device of the present invention is an organic EL display device having a substrate, an organic EL layer and a second electrode. The substrate has a first electrode, a pixel segmentation layer and a spacer on the substrate. When the maximum value of the surface roughness (Ra1) of the pixel segmentation layer and the surface roughness (Ra2) of the spacer is set as Ramax, Ramax is 1.0 nm or more and 50 nm or less.
[0015] Furthermore, the manufacturing method of the organic EL display device of the present invention is a method for manufacturing an organic EL display device having the following substrate, organic EL layer and second electrode, wherein the substrate has a first electrode, a pixel segmentation layer and spacers on a substrate, and the manufacturing method includes a step of processing the pixel segmentation layer and spacers together, wherein the photomask used for processing together is a halftone photomask having a light-transmitting part, a light-blocking part and a semi-light-transmitting part.
[0016] The effects of the invention
[0017] Regarding the organic EL display device of the present invention, an organic EL display device including the formation of a pixel dividing layer and spacers can be manufactured by a simple method without peeling off the organic EL layer, and external light reflection can be suppressed by increasing the diffusion reflection of the substrate. Attached Figure Description
[0018] [ Figure 1 [This is a schematic cross-sectional view of the organic EL display device of the present invention.]
[0019] [ Figure 2 [Image 1] is a schematic cross-sectional view of a substrate as an example of the present invention.
[0020] [ Figure 3 [A schematic cross-sectional view of Ra1 and Ra2 in this invention.]
[0021] [ Figure 4 [This is a schematic diagram of the cone angle of the pixel segmentation layer in this invention.]
[0022] [ Figure 5 [This is a schematic cross-sectional view of a typical organic EL display device.]
[0023] [ Figure 6 [This is a schematic diagram of the first electrode and halftone mask according to an embodiment of the present invention.]
[0024] [ Figure 7 [This is a schematic diagram of a bending test according to an embodiment of the present invention.]
[0025] [ Figure 8 [This is a schematic diagram of an organic EL display device according to an embodiment of the present invention.]
[0026] [ Figure 9 [This is a schematic diagram of the light-emitting element in an embodiment of the present invention.] Detailed Implementation
[0027] The following describes in detail the methods for carrying out the present invention (hereinafter referred to as "implementation methods"). It should be noted that the present invention is not limited to the embodiments described below.
[0028] <Organic EL Display Device>
[0029] The organic EL display device of the present invention is an organic EL display device having a plurality of display pixels formed in a matrix. Based on the direction in which light is extracted from the organic EL layer, it is generally classified into top-emitting and bottom-emitting types, but there is no particular limitation. Furthermore, based on the driving method, it is also generally classified into passive driving type, where electrodes are divided into columns and rows and only the display pixels sandwiched between the electrodes emit light, and active driving type, where a plurality of TFTs are disposed in each display pixel and switched on and off, without particular limitation.
[0030] The organic EL display device of the present invention is an organic EL display device having a substrate, an organic EL layer and a second electrode. The substrate has a first electrode, a pixel segmentation layer and a spacer on the substrate. When the maximum value of the surface roughness (Ra1) of the pixel segmentation layer and the surface roughness (Ra2) of the spacer is set as Ramax, Ramax is 1.0 nm or more and 50 nm or less.
[0031] Figure 1A schematic cross-sectional view of an organic EL display device as an example of the present invention is shown. In the organic EL display device, a first electrode 2 is provided on a substrate 1. On the substrate 1, a pixel dividing layer 3 is provided in the area where the first electrode 2 is not present (hereinafter, the area on the substrate 1 where the first electrode 2 is not present is sometimes referred to as the gap of the first electrode). In addition, spacers 4 are provided on the pixel dividing layer. In the organic EL display device, the unit having the first electrode, pixel dividing layer and spacers on the above-mentioned substrate is referred to as a substrate. Furthermore, by having an organic EL layer 5 and a second electrode 6 on the substrate, an organic EL display device is formed.
[0032] <Substrate>
[0033] In the organic EL display device of the present invention, the substrate is defined as a minimum unit comprising only the substrate 1, the first electrode 2, the pixel segmentation layer 3, and the spacer 4, as described later. If this minimum unit is included, the substrate can be configured to also include wiring, TFTs 7, patterned antennas, and a planarization layer 8, etc. (for example, Figure 2 (The composition of the substrate). In this invention, the above-mentioned wiring, TFT7, sensor type, patterned antenna, and planarization layer 8, which serve as the substrate of the first electrode 2, are all considered as part of the substrate 1.
[0034] Most of the wiring is connected to external devices via FPC (Flexible Printed Circuit) used for driving. In addition to TFT7, sensors such as cameras, ID sensors, fingerprint readers, and illuminance sensors, as well as patterned antennas for communication and power supply, can also be installed. In this substrate 1 that integrates multiple functions, a planarization layer 8 is preferably provided. By providing the planarization layer 8, the wiring, TFT7, and other irregularities are covered before the first electrode 2 is formed, thus planarizing the substrate 1. Planarizing the substrate 1 prevents defects in the first electrode 2, pixel segmentation layer 3, and spacers 4 provided on the substrate, resulting in a high-quality substrate. Figure 2 A schematic cross-sectional view of a substrate, which is an example of the present invention, is shown.
[0035] <Substrate>
[0036] As Figure 1 Substrate 1 and Figure 2 The substrate 1a of the substrate 1 below the TFT7 can be appropriately selected from materials such as metal, glass, and resin film, which are preferred for supporting the display device and handling in subsequent processes. Especially when flexibility is required, resin film is preferred.
[0037] As the type of glass, soda-lime glass, alkali-free glass, etc., can be used. The thickness of the glass only needs to be sufficient to ensure mechanical strength. Regarding the glass material, the fewer leached ions from the glass, the better; therefore, alkali-free glass is preferred, but soda-lime glass with a barrier coating such as SiO2 can also be used.
[0038] From the perspective of excellent light transmittance, the resin material used in the resin film is preferably a resin material selected from polybenzoxazole resin, polyamide-imide resin, polyimide resin, polyamide resin, and poly(p-xylene) resin. The substrate may contain these resin materials individually or in combination.
[0039] For example, in the case where the substrate is formed from polyimide resin, it can also be formed by coating a solution containing polyamic acid (containing a portion of imidized polyamic acid) or soluble polyimide resin as a precursor of polyimide resin onto a support substrate and then firing it.
[0040] Furthermore, since the aforementioned light-emitting elements are known to have poor tolerance to oxygen and moisture, a suitable gas barrier layer can be incorporated into the substrate. In particular, in the case of resin films, by using layered inorganic thin films, a display device with high reliability can be obtained. In addition, the substrate can be provided with wiring, TFTs (7), planarization layers (8), etc.
[0041] <First Electrode>
[0042] Regarding the first electrode 2 in this invention, in the case of bottom-emitting type, it needs to be a light-transmitting electrode, and in the case of top-emitting type, it needs to be a light-reflecting electrode.
[0043] For bottom-emitting types, for example, transparent conductive metal oxides such as tin oxide, indium oxide, and indium tin oxide (ITO), or metals such as gold, silver, and chromium, inorganic conductive materials such as copper iodide and copper sulfide, and conductive polymers such as polythiophene, polypyrrole, and polyaniline can be used, without any particular limitation.
[0044] For top-emitting types, materials exhibiting high reflectivity and low resistance to visible light are preferred, especially those with a certain thickness. Furthermore, material selection must consider the weather resistance in subsequent processes such as wet etching, cleaning, storage, and use. Ag or Ag alloy films containing Ag as the main component are particularly useful due to their high reflectivity. Ag alloy films can be made from AgPdCu, AgTiCu, etc., with Ag as the main component. Laminating these Ag alloy films with oxide conductive films such as ITO or IZO films can achieve low contact resistance with the organic EL layer, making them preferred. Additionally, Al or Al alloy films containing Al as the main component are also good as the first electrode for top-emitting types. Al-Ni alloy films containing 0.1 to 2 atomic percent Ni have the same high reflectivity as pure Al, making them preferred. Furthermore, reflective metal films such as molybdenum (Mo) and tungsten (W) can also be used.
[0045] Regarding the resistance of the first electrode, there is no limitation as long as it can supply sufficient current for the light-emitting element to emit light. However, from the viewpoint of the power consumption of the light-emitting element, low resistance is desirable. For example, ITO with a resistance of 300 Ω / □ or less functions as an electrode for the element. Currently, ITO with a resistance of around 10 Ω / □ can also be supplied, so low-resistance products are particularly desirable. The thickness of the first electrode can be arbitrarily selected according to characteristics such as transmittance and resistance value, and is usually used in the range of 100 to 300 nm.
[0046] The first electrode can be formed using known methods. For example, it can be patterned by etching using a photoresist after forming a film using a vacuum film deposition method such as sputtering.
[0047] <Pixel Segmentation Layer>
[0048] In the organic EL display device of the present invention, a pixel segmentation layer 3 is formed in the gap of the first electrode 2. By forming the pixel segmentation layer in the gap of the first electrode, display pixels can be segmented. That is, by patterning the pixel segmentation layer in the gap of the first electrode, the exposed portion of the first electrode is limited, and only the opening of the pixel segmentation layer functions as a display pixel. In addition, by covering the periphery of the linear or island-shaped first electrode with the pixel segmentation layer, short circuits occurring at the edge of the first electrode and line breaks in the second electrode can be prevented, thereby improving the reliability of the display device. It should be noted that, in the organic EL display device of the present invention, the pixel segmentation layer may also be formed in a location other than the gap of the first electrode, as needed.
[0049] In this invention, when the maximum value of the surface roughness (Ra1) of the pixel segmentation layer and the surface roughness (Ra2) of the spacer is set as Ramax, Ramax is 1.0 nm or more and 50 nm or less. Furthermore, it is more preferable that the surface roughness (Ra1) of the pixel segmentation layer is Ramax. Alternatively, both the surface roughness (Ra1) of the pixel segmentation layer and the surface roughness (Ra2) of the spacer may be Ramax.
[0050] It should be noted that, in this invention, the atomic force microscope (AFM) used for surface roughness measurement is generally used to measure the substrate of an organic EL display device placed on a horizontal plane from a vertical position. The object ranges of Ra1 and Ra2 are shown in the figure. Figure 3 Therefore, in this invention, "the surface roughness of the pixel segmentation layer" refers to the surface roughness of the surface of the pixel segmentation layer that is in contact with the organic EL layer and can be measured using AFM, i.e., the surface that is approximately parallel to the substrate.
[0051] Furthermore, since spacers are formed on the pixel segmentation layer, the portion without spacers becomes the interface with the organic EL layer. Conventionally, poor adhesion between the pixel segmentation layer and the organic EL layer has led to easy delamination, a significant problem, particularly in flexible products. In this invention, by setting the surface roughness (Ra1) of the pixel segmentation layer to 1.0 nm or more, an anchoring effect can be achieved; more preferably, it is 5.0 nm or more, and more preferably 20 nm or more, thereby improving the adhesion with the organic EL layer.
[0052] Furthermore, regarding the surface roughness (Ra1) of the pixel segmentation layer, an anchoring effect can be achieved as long as it is 1.0 nm or more. However, for the purpose of suppressing pinholes in the second electrode and defects in the sealing process described later, it is preferable to make it 50 nm or less. Moreover, while improving adhesion through a large Ra1, it is effective to ensure that the interface between the pixel segmentation layer and the organic EL layer is as large as possible. When Ra1 is greater than the surface roughness Ra2 of the spacer described later, i.e., Ra1 becomes Ramax, the area of the interface between the pixel segmentation layer and the organic EL layer is preferably 50% or more of the total area of the interface between the substrate and the organic EL layer. This means that the pixel segmentation layer is 50% or more of the surface area of the substrate.
[0053] Furthermore, since the shape of the edge of the pixel segmentation layer can be a cause of breakage in the second electrode, a gently sloping positive cone shape is preferred. Here, a positive cone shape refers to a state where the angle (hereinafter, this angle is sometimes referred to as the cone angle of the pixel segmentation layer) between the tangent at the interface between the first electrode and the pixel segmentation layer and the tangent at a position where the maximum thickness of the pixel segmentation layer is 50% of the film thickness in the surface of the cone portion of the pixel segmentation layer is less than 90 degrees. In this invention, in order to obtain a display device with high reliability that suppresses breakage in the second electrode, the cone angle of the pixel segmentation layer is preferably less than 60 degrees, and more preferably less than 50 degrees.
[0054] use Figure 4 The cone angle of the pixel segmentation layer will be explained in detail. Figure 4 In the image, a first electrode 2 is provided on a substrate 1. A pixel segmentation layer 3 is provided in the gap of the first electrode 2, and a spacer 4 is provided on the pixel segmentation layer. The angle (B) formed by the tangent at the interface between the first electrode and the pixel segmentation layer and the tangent at a position (point A) on the surface of the tapered portion of the pixel segmentation layer where the maximum thickness of the pixel segmentation layer is 50% of the film thickness is defined as the cone angle of the pixel segmentation layer.
[0055] As a pixel dividing layer, it is not limited to any known organic or inorganic material. From the perspective of easy adjustment of surface roughness, the pixel dividing layer preferably comprises a cured film of a photosensitive resin composition containing an alkali-soluble resin. The pixel dividing layer can be a single layer or multiple layers. For example, when the pixel dividing layer is multiple layers, the surface that is substantially parallel to the substrate, which is the object of surface roughness measurement, is preferably a cured film of a photosensitive resin composition containing an alkali-soluble resin.
[0056] The photosensitive resin composition preferably contains (A) an alkali-soluble resin, (B) a photosensitizer, and (C) an organic solvent, and may also contain (D) a coloring material and (E) a hydrophobic material. As a photosensitive resin composition, by combining (A) an alkali-soluble resin and (B) a photosensitizer, pattern processing utilizing photosensitivity can be achieved. Furthermore, by containing (C) an organic solvent, a varnish-like state can be formed, which can sometimes improve coatability. In addition, by including (D) a coloring material in the photosensitive resin composition, the pixel segmentation layer can be blackened. Furthermore, by including (E) a hydrophobic material, the pixel segmentation layer can be given hydrophobicity. Due to the differences in exposure sensitivity and dissolution rate between these (D) coloring materials, (E) hydrophobic materials, and (A) alkali-soluble resin, the surface roughness of the pixel segmentation layer and the spacers increases after using the halftone mask process described later, and the surface roughness of the pixel segmentation layer and the spacers can be adjusted separately, which is therefore preferable. The photosensitive resin composition may also contain other components.
[0057] The pixel segmentation layer can be formed using known methods. Among these, wet coating is preferred from the perspective of being able to uniformly form a thin film on a large substrate. Examples of wet coating methods include spin coating, slot coating, dip coating, spray coating, and printing.
[0058] The thickness of the pixel segmentation layer is typically 0.3 μm to 10 μm, as long as it is sufficient to cover the unevenness of the first electrode; there are no particular limitations. Furthermore, the pixel segmentation layer must be patterned, as residue from the removed portion can sometimes directly lead to defects such as short circuits and black spots. Additionally, to support the structure covering the second electrode in subsequent processes and ensure the strength of the display device, spacers need to be fabricated on the pixel segmentation layer.
[0059] <(A) Alkali-soluble resin>
[0060] In this invention, alkali solubility refers to the following: a solution obtained by dissolving resin in γ-butyrolactone (GBL) is coated onto a silicon wafer and pre-baked at 120°C for 4 minutes to form a pre-baked film with a thickness of 10 μm ± 0.5 μm. The pre-baked film is then immersed in a 2.38% by mass tetramethylammonium hydroxide aqueous solution at 23°C ± 1°C for 1 minute and rinsed with pure water. The dissolution rate, calculated based on the reduction in film thickness at this point, is above 50 nm / min.
[0061] From the perspective of improving heat resistance, (A) the alkali-soluble resin preferably has an aromatic carboxylic acid structure. It should be noted that, in this invention, the aromatic carboxylic acid structure refers to a carboxylic acid structure that is directly covalently bonded to an aromatic ring.
[0062] As (A) the alkali-soluble resin, it is preferred to contain one or more resins selected from the group consisting of acrylic resin, phenolic resin, polysiloxane resin, Cardo resin, polyimide resin, polyimide precursor resin, polybenzoxazole resin, and polybenzoxazole precursor resin.
[0063] Among these resins, considering the ability to simultaneously achieve heat resistance and chemical resistance, (A) the alkali-soluble resin preferably contains polyimide resin, polyimide precursor resin, polybenzoxazole resin, and / or polybenzoxazole precursor resin. High chemical resistance results in less film loss during wet etching of the pixel segmentation layer, which is therefore preferable. Furthermore, polyimide precursor resin is particularly preferred for its low gas emission under high-temperature conditions. Moreover, polyimide precursor resin having an ammonium acid structure is more preferred for improving alkali solubility.
[0064] <Silica particles in pixel segmentation layer>
[0065] The pixel segmentation layer in the organic EL display device of the present invention preferably contains (a) silica particles with a primary particle size of 5 to 30 nm (hereinafter, sometimes referred to as component (a)). More preferably, in addition to containing component (a), the pixel segmentation layer also contains a (D) coloring material as described later. In this case, it is further preferable to contain an (D1) organic pigment as described later as the (D) coloring material, and even more preferably to contain component (b) as the (D1) organic pigment as described later. Furthermore, component (a) preferably has a primary particle size of 5 to 30 nm and an aspect ratio (major axis / minor axis) of 1.0 to 1.5. By containing component (a), the uniformity of the opening width of the opening is improved, thereby reducing brightness unevenness. The primary particle size referred to herein is the major axis of the particle, and silica particles with a primary particle size of 5 to 30 nm refer to particles whose primary particle size is within the range of 5 to 30 nm. The "aspect ratio (major diameter / minor diameter)" referred to here is the value obtained by rounding the major diameter to the minor diameter in the first diameter of silica particles to the second decimal place.
[0066] The term "silica particles" as used herein refers to particles containing 90% or more SiO2 by weight after water removal, particles formed from silica (silicic anhydride), particles formed from silica hydrates (hydrated silicic acid), and particles formed from quartz glass. The form in which hydrated silicic acid exists is not particularly limited; particles formed from orthosilicic acid, metasilicic acid, and / or metadisilicic acid also fall under the category of silica particles as used herein. Weight after water removal refers to the weight of the particles minus the weight of the water content within the particles.
[0067] However, in core-shell composite particles, surface treatment agents and coatings applied as shells on at least a portion of the surface of particles that do not contain SiO2 as a core, such as particles formed from organic polymers, organic pigments, or inorganic pigments, are defined as not belonging to silica particles when alone, regardless of the SiO2 content. On the other hand, core-shell composite particles containing SiO2 in the core and having a SiO2 content of 90% by weight or more after removing water are defined as belonging to silica particles. That is, component (a) fills the pixel segmentation layer as particles dispersed in the pixel segmentation layer. The particle structure of component (a) is not particularly limited and may have internal voids.
[0068] Other than the aforementioned particles formed from silicon dioxide, particles formed from silicon dioxide hydrates, and particles formed from quartz glass, examples of silicon dioxide particles formed from composite oxides of silicon and metals, with a SiO2 content of 90% by weight or more after water removal, are provided. Examples of metals referred to herein include zirconium, titanium, and cerium. Silicon dioxide particles containing hafnium atoms are defined as mixtures of silicon dioxide particles and hafnium atoms (hereinafter sometimes referred to as component (c)).
[0069] From the perspective of further reducing brightness unevenness in organic EL display devices, (a) the composition more preferably contains silica particles with a primary particle size of 5 to 20 nm, and more preferably contains silica particles with a primary particle size of 5 to 15 nm. The primary particle size referred to here is the major axis of the silica particles. More preferably, it contains silica particles with an aspect ratio of 1.0 to 1.3, and more preferably, it contains silica particles with an aspect ratio of 1.0 to 1.2. It should be noted that when the aspect ratio is 1.0, it can be considered as spherical silica particles.
[0070] The silica particles other than component (a) can be identified and determined based on elemental mapping information as follows: A specimen obtained by thinly cutting the pixel segmentation layer and spacer layer is used as the observation sample. The smoothness of the cross-section is improved by grinding, preferably through a pretreatment based on ion milling, and more preferably through a pretreatment based on focused ion beam (FIB) processing. For this improved smoothness cross-section, the portion of the pixel segmentation layer or spacer layer located in the film depth direction from the outermost layer, within the range of 0.2–0.8 μm, is analyzed using transmission electron microscopy-energy dispersive X-ray spectroscopy (TEM-EDX). Alternatively, transmission electron microscopy-electron energy loss spectroscopy (TEM-EELS) or scanning transmission electron microscopy-energy dispersive X-ray spectroscopy (STEM-EDX) can also be used for analysis.
[0071] Specifically, the image analysis particle size distribution measuring machine "Mac-View" (manufactured by MOUNTECH) was used to measure images of samples obtained by transmission electron microscopy-energy dispersive X-ray spectroscopy (TEM-EDX) at 50,000x magnification. This allowed for the differentiation between silica particles belonging to component (a) and those not belonging to component (a). Specifically, in the cross-section of the pixel segmentation layer, 30 silica particles were randomly selected from the TEM images, and their major axis, minor axis, and aspect ratio were measured. Silica particles with a major axis (nm) of 5–30 nm and an aspect ratio in the range of 1.0–1.5 were defined as component (a). It should be noted that for a single silica particle, if the minor axis and major axis are equal in the TEM image (i.e., a perfect circle), its diameter is considered the major axis. As representative values representing the characteristics of silica particles belonging to component (a), the average particle size, i.e., the average major diameter, is calculated, and the value obtained by rounding to the first decimal place is calculated. The average aspect ratio, i.e., the average aspect ratio of each silica particle belonging to component (a), is also calculated, and the value obtained by rounding to the second decimal place is used. Here, SiO2 that has interfaces with the surface of particles such as polymer-formed particles, organic pigments, and / or inorganic pigments is excluded from the analysis. The major diameter and aspect ratio of silica particles contained in the spacer layer can also be determined using the same method.
[0072] Furthermore, the pixel segmentation layer of the organic EL display device of the present invention may also contain silicon dioxide particles that are not part of component (a), namely, silicon dioxide particles having a primary particle size of less than 5 nm or more than 30 nm, or silicon dioxide particles with an aspect ratio (major diameter / minor diameter) of more than 1.5. Examples of silicon dioxide particles that are not part of component (a) include, for example, "Admafine" (registered trademark) SO-E2, SO-E4 (all of which are manufactured by Admatechs Corporation), KE-P10, and KE-S10 (all of which are manufactured by Nippon Shokubai Co., Ltd.).
[0073] The pixel segmentation layer of the organic EL display device of the present invention may further contain particles that contain SiO2 in a proportion of less than 90% by weight after removing water, and which are not silicon dioxide particles as described in this specification. For example, "ATLAS" (registered trademark) 100 (manufactured by CABOT Corporation), which is an organic-inorganic composite particle with a silicon dioxide:polymer ratio of 70:30 by weight, disclosed in Japanese Patent Application Publication No. 2018-97251, is an example.
[0074] From the viewpoint of suppressing brightness unevenness, the average primary particle size of the silica particles contained in the pixel segmentation layer of the organic EL display device of the present invention is preferably 5 to 30 nm, more preferably 5 to 25 μm. The average aspect ratio (major diameter / minor diameter) is preferably 1.0 to 1.3, more preferably 1.0 to 1.2. That is, even if the pixel segmentation layer of the organic EL display device of the present invention contains silica particles that are not part of component (a), it is preferable that the average primary particle size of all the silica particles contained therein is 5 to 30 nm. In addition, similarly, it is preferable that the average aspect ratio (major diameter / minor diameter) is 1.0 to 1.3. The silica particles referred to herein include both component (a) and silica particles that are not part of component (a). The average primary particle size referred to here is: for the aforementioned image obtained by observing a cross-section ranging from 0.2 to 0.8 μm in the film depth direction from the outermost layer of the pixel segmentation layer using transmission electron microscopy-energy dispersive X-ray spectroscopy (TEM-EDX) at 50,000x magnification, 30 silica particles were randomly selected using an image analysis particle size distribution measuring machine (Mac-View, MOUNTECH), and the average of the major diameters of all silica particles was rounded to the first decimal place. The "average aspect ratio (major diameter / minor diameter)" referred to here is: the average of the major diameter divided by the minor diameter of each of the 30 randomly selected silica particles in the image, and the average of the resulting average was rounded to the second decimal place. Silica particles with an average primary diameter of 5–30 nm refer to particles whose average primary diameter is within the range of 5–30 nm. Silica particles with an average aspect ratio of 1.0–1.3 refer to particles whose average aspect ratio is within the range of 1.0–1.3.
[0075] The specific surface area of component (a) corresponding to the aforementioned primary particle size is preferably 50 to 500 m². 2 / g, more preferably 200-400m 2 / g. The specific surface area referred to here is the specific surface area measured using the BET method with nitrogen as the adsorbed gas. (a) The surface of the component can be porous or non-porous, and can have an internal surface area.
[0076] As functional groups present on the surface of component (a), examples include reactive residues containing surface-modifying groups of olefinic unsaturated double bonds, silanol groups, alkoxysilyl groups, trialkylsilyl groups, and diphenylsilyl groups. From the viewpoint of further reducing brightness unevenness, reactive residues containing surface-modifying groups of olefinic unsaturated double bonds are preferred. The reactive residues containing surface-modifying groups of olefinic unsaturated double bonds referred to herein are groups remaining after the olefinic unsaturated double bond group of the surface-modifying group of olefinic unsaturated double bonds undergoes a free radical polymerization reaction with light and / or heat. More preferably, component (a) contains silica particles having reactive residues containing surface-modifying groups of olefinic unsaturated double bonds on the particle surface, and the reactive residues containing surface-modifying groups of olefinic unsaturated double bonds have the structure represented by formula (3) and / or the structure represented by formula (4). The reactive residue containing the surface-modifying group of the olefinic unsaturated double bond is more preferably a residue generated by radical polymerization with a compound having two or more free radical polymerizable groups in the molecule, as described later.
[0077] [Chemical Formula 1]
[0078]
[0079] In equation (3), R 17 16 Represents a hydrogen atom or a methyl group. R 18 17 This represents a divalent hydrocarbon group with 1 to 7 carbon atoms. j and k are integers, each independently representing 0 or 1. Specifically, when j is 1, k is 1. * 1 This indicates the bonding site with a carbon atom.
[0080] * 2 This refers to the bonding sites on the surface of silicon dioxide particles that are bonded to oxygen atoms that are also bonded to silicon atoms. R 19 18 This represents an alkyl group with 1 to 3 carbon atoms. m and n are integers, where m represents 1 to 3 and n represents 0 to 2. Among these, m + n = 3.
[0081] [Chemical Formula 2]
[0082]
[0083] In equation (4), R 20 19 Represents a hydrogen atom or a methyl group. R 21 20 This represents an oxidized alkenyl group with 1 to 3 carbon atoms. r is an integer, representing 1 to 4. * 3 This indicates the bonding site with a carbon atom.
[0084] * 4 This refers to the bonding sites on the surface of silicon dioxide particles that are bonded to oxygen atoms that are also bonded to silicon atoms.
[0085] The component (a) having the structure represented by formula (3) can be obtained by introducing a surface modification group derived from an organoalkoxysilane compound having an alkene-type unsaturated double bond group through a dehydration condensation reaction with the silanol group on the surface of silica particles, and by allowing the alkene-type unsaturated double bond group contained in the surface modification group to undergo a free radical polymerization reaction through light and / or heat.
[0086] Examples of organoalkoxysilane compounds having olefinic unsaturated double bond groups include vinyltrimethoxysilane, vinyltriethoxysilane, p-styryltrimethoxysilane, p-styryltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropylmethyldimethoxysilane, 3-acryloxypropylmethyldiethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-acryloxypropyltriethoxysilane, allyltrimethoxysilane, and allyltriethoxysilane.
[0087] The component (a) having the structure represented by formula (4) can be obtained by introducing a surface-modifying group derived from an isocyanate compound having an olefinic unsaturated double bond group through a carbamate reaction with the silanol group on the surface of silica particles, and by subjecting the olefinic unsaturated double bond group contained in the surface-modifying group to a free radical polymerization reaction by light and / or heat. Examples of isocyanate compounds having olefinic unsaturated double bond groups include, for example, 2-methacryloyloxyethyl isocyanate, 2-acryloyloxyethyl isocyanate, and 2-(2-methacryloyloxyethyloxy)ethyl isocyanate.
[0088] In addition, by sequentially modifying the surface of silica particles with surface-modifying groups derived from organoalkoxysilane compounds having alkene-type unsaturated double bond groups and isocyanate compounds having alkene-type unsaturated double bond groups, it is possible to obtain component (a) with the structure represented by formula (3) and the structure represented by formula (4) of the reaction residues.
[0089] For example, to improve the dispersion stability of component (a) in a negative photosensitive composition, component (a) preferably has a trialkylsilyl group, more preferably a trimethylsilyl group. A trimethylsilylating agent is used to convert hydrogen atoms in the silanol groups on the surface of silica particles into trimethylsilyl groups, thereby allowing the trimethylsilyl group to be introduced into component (a). Examples of trimethylsilylating agents include hexamethyldisilazane and trimethylalkoxysilane, which can be introduced via deamination and dehydration condensation reactions, respectively. By improving the dispersion stability of component (a), brightness unevenness can sometimes be reduced more stably.
[0090] From the perspective of further reducing brightness unevenness, (a) the component preferably contains silica particles having sodium atoms. Examples of sodium atom forms include, for instance, sodium ions (Na+). + (a) and its salt with silanol groups (Si-ONa). The sodium atom content in component (a) is preferably 100 to 5000 ppm by weight. Silica particles containing sodium atoms can be synthesized by reacting strongly alkaline sodium silicate, which serves as a silicon source, with an inorganic acid, which serves as a strong acid, under alkaline conditions. It should be noted that the sodium atoms in the silica particles can be detected using the aforementioned TEM-EDX method, at the center of the intersection of the major and minor axes in a cross-sectional image of the primary particle.
[0091] Regarding the content of component (a), from the perspective of suppressing brightness unevenness, in the pixel segmentation layer, the content is preferably 1 to 50% by weight (SiO2 equivalent), more preferably 5 to 20% by weight. Furthermore, from the same viewpoint, for all silica components in the pixel segmentation layer, the content is preferably 1 to 50% by weight (SiO2 equivalent), more preferably 7 to 30% by weight. The content referred to here as SiO2 equivalent means the content calculated by removing the weight of moisture in the silica particles, which varies due to thermal processes, based on the technical knowledge of those skilled in the art.
[0092] From the perspective of further reducing brightness unevenness, the pixel segmentation layer in the organic EL display device of the present invention preferably contains 1 to 50 ppm by weight of (c) hafnium atoms (hereinafter, sometimes referred to as (c) component). More preferably, it is 1 to 30 ppm by weight. As (c) component, it is preferably contained in the pixel segmentation layer as inorganic particles containing hafnium atoms.
[0093] Examples of inorganic particles containing component (c) include hafnium oxide (HfO2), composite oxides of metals other than hafnium and hafnium, solid solutions of oxides of metals other than hafnium and hafnium oxide, hafnium oxynitride, composite oxynitrides of metals other than hafnium and hafnium, and solid solutions of oxynitrides of metals other than hafnium and hafnium oxynitride. Among these, hafnium oxide (HfO2) or composite oxides of metals other than hafnium and hafnium are preferred from the viewpoint of excellent effect in reducing brightness unevenness, and zirconium-hafnium composite oxides (ZrO2-HfO2) are more preferred.
[0094] As the inorganic particles containing component (c), commercially available products that can be obtained in powder form can be used, such as Hafnium oxide P, Hafnium oxide R, Hafnium oxide S (all manufactured by ATI METALS), and Hafnium oxide microparticles (manufactured by High Purity Chemical Research Institute Co., Ltd.). Alternatively, during the preparation of the pigment dispersion containing component (b) described later, microparticles generated by wet grinding of the surface of a pulverizing medium containing component (c) using mechanical energy can be co-dispersed with component (b), thereby incorporating component (c) into the final pixel segmentation layer.
[0095] Regarding the content of component (c), a portion of the pixel segmentation layer located in the depth direction of the film, ranging from 0.2 to 0.8 μm, can be cut out from the outermost layer. This portion is then heated and ashed in an electric furnace at a temperature above 800°C. Following this, it is decomposed by heating with sulfuric acid, nitric acid, and hydrofluoric acid, and finally dissolved by heating with dilute hydrochloric acid to obtain a solution. This solution is used as the analytical sample, and quantification is performed using ICP (Inductively Coupled Plasma) luminescence spectrophotometry. The analytical apparatus can be a PS3520VDDII (manufactured by Hitachi High-Tech Science).
[0096] <(D) Coloring Materials>
[0097] When coloring is required from the viewpoint of light-shielding and anti-reflection, the photosensitive resin composition used in this invention preferably contains a (D) coloring material. By including a (D) coloring material in the photosensitive resin composition, the pixel segmentation layer becomes a layer containing the (D) coloring material, achieving the effects described later, which is therefore preferable. The (D) coloring material is a compound that absorbs light of a specific wavelength, particularly a compound that colors light by absorbing wavelengths of visible light (380–780 nm). By including the (D) coloring material, the cured film obtained from the photosensitive resin composition can be colored, imparting the coloring property that light transmitted through the cured film of the photosensitive resin composition or light reflected from the cured film of the photosensitive resin composition is colored to the desired color. Furthermore, it imparts the light-shielding property that blocks light of the wavelengths absorbed by the (D) coloring material from light transmitted through the cured film of the photosensitive resin composition or light reflected from the cured film of the photosensitive resin composition.
[0098] The content of the (D) coloring material used in this invention is preferably 1% by weight or more in the pixel segmentation layer, more preferably 10% by weight or more, and even more preferably 15% by weight or more. If the content ratio is within the above range, the light-blocking property, coloring property, or tonal property can be improved. On the other hand, the content ratio is preferably 70% by weight or less, more preferably 65% by weight or less, and even more preferably 60% by weight or less. If the content ratio is within the above range, the sensitivity during exposure can be improved.
[0099] Examples of (D) coloring materials include known compounds such as (D1) organic pigments, (D2) inorganic pigments, and (D3) dyes that absorb wavelengths of visible light and are colored in white, red, orange, yellow, green, blue, or purple. Two or more of these coloring materials can be used in combination, as can two or more colors. Combining two or more colors results in a pixel segmentation layer that also possesses the effects described later, and is therefore preferred. Combining two or more colors improves the color tuning property by adjusting the light transmitted through the cured film of the photosensitive resin composition, or the light reflected from the cured film of the photosensitive resin composition, to the desired color coordinates.
[0100] By using (D1) organic pigments as (D) coloring materials, the characteristics of (D1) organic pigments, namely chemical structure changes or functional group transformation functions, can be utilized to transmit or block light of a desired specific wavelength, thereby adjusting the transmission or absorption spectrum of the cured film of the photosensitive resin composition and improving its tonal properties. Details regarding such (D1) organic pigments will be presented later.
[0101] By using (D2) inorganic pigments as (D) coloring materials, the heat resistance and weather resistance of the cured film of the photosensitive resin composition can be improved due to the characteristics of (D2) inorganic pigments, namely their excellent heat resistance and weather resistance. Examples of (D2) inorganic pigments include, for example, zirconium nitride, zirconium oxide, titanium oxide, barium carbonate, zinc white, zinc sulfide, lead white, calcium carbonate, barium sulfate, silica, bauxite white, silicon dioxide, kaolin, talc, bentonite, iron oxide red, molybdenum chromium red, molybdenum chromium orange, chromium vermilion, yellow lead, cadmium yellow, yellow iron oxide, titanium yellow, chromium oxide, chromium green, titanium cobalt green, cobalt green, cobalt chromium green, Victoria green, ultramarine, Prussian blue, cobalt blue, sky blue, cobalt silica blue, cobalt zinc silica blue, manganese violet, cobalt violet, graphite or silver-tin alloy; or particles, oxides, complex oxides, sulfides, sulfates, nitrates, carbonates, nitrides, carbides or nitrogen oxides of metals such as titanium, copper, iron, manganese, cobalt, chromium, nickel, zinc, calcium or silver.
[0102] In order to achieve a surface roughness (Ra1) of 1.0 nm to 50 nm for the pixel segmentation layer, it is preferable to disperse inorganic pigments with a high specific gravity, such as zirconium nitride. This is because, as will be explained later, pigment precipitation is expected during development in the pixel segmentation layer, which belongs to the halftone exposure area. Inorganic pigments suffer from problems such as pigment aggregation, thickening, and decreased sensitivity over time. However, by setting the acid equivalent of component (A) to 200 g / mol or more and 500 g / mol or less, the alkali solubility of the exposed, unexposed, and halftone exposure areas described later can be appropriately adjusted. If the acid equivalent of component (A) is less than 200 g / mol, for example, when obtaining a cured film of a positive photosensitive resin composition, the alkali solubility of the unexposed area becomes high, and the difference in dissolution rate between the unexposed and exposed areas is small, making it impossible to form the desired pattern. By setting the acid equivalent to 200 g / mol or more, the solubility of the unexposed area can be suppressed, and a pattern with less residue at the openings due to the adhesion of dissolution from the unexposed area can be formed. In addition, by making the acid equivalent of component (A) less than 500 g / mol, the dispersion and stabilization of zirconium nitride particles can be promoted, resulting in a photosensitive resin composition with excellent storage stability.
[0103] (D3) Dyes are compounds that color an object through chemical adsorption or strong interaction between the dye's ionic groups or substituents such as hydroxyl groups and the surface structure of the object. They are usually soluble in solvents. Furthermore, regarding the coloring effect of dyes, since the molecules adsorb onto the object individually, the tinting strength and color development efficiency are high. Dyes can be classified, for example, as direct dyes, reactive dyes, sulfur dyes, uranium dyes, acid dyes, metal-containing dyes, metal-containing acid dyes, basic dyes, mordant dyes, acid mordant dyes, disperse dyes, cationic dyes, or fluorescent whitening dyes, etc. Based on the material system, anthraquinone dyes, azo dyes, azazine dyes, phthalocyanine dyes, methine dyes, oxazine dyes, quinoline dyes, indigo dyes, indigo dyes, carbocation dyes, vat dyes, pyrene dyes, perylene dyes, triarylmethane dyes, or xanthones dyes can be cited. From the viewpoint of solubility and heat resistance in (C) organic solvents, anthraquinone dyes, azo dyes, azazine dyes, methine dyes, triarylmethane dyes, and xanthones dyes are preferred.
[0104] In order to make the surface roughness (Ra1) of the pixel segmentation layer 1.0 nm to 50 nm, it is preferable to use a salt-forming compound (D3-1) formed by acidic and basic dyes as the (D) coloring material. The reason is that by containing a salt-forming compound (D3-1) formed by acidic and basic dyes, dye precipitation is expected during development in the pixel segmentation layer belonging to the halftone exposure area.
[0105] (D3-1) Salt-forming compounds formed by acid dyes and basic dyes refer to compounds obtained by reacting acid dyes with basic dyes. These compounds are chemically stable and are produced through a chemical (salt-forming) reaction between an acid dye with an anionic dye ion and a basic dye with a cationic dye ion.
[0106] Acid dyes refer to compounds with acidic substituents such as sulfonyl and carboxyl groups in their molecules, or anionic water-soluble dyes that are salts of these compounds. It should be noted that acid dyes include dyes with acidic substituents such as sulfonyl and carboxyl groups that are classified as direct dyes. Among these, acid dyes containing xatonium-based acid dyes are preferred for reducing residue at the opening. For further reducing residue at the opening, xatonium-based acid dyes more preferably contain rhodamine-based acid dyes such as CI Acid Red 50, 52, and 289. Furthermore, for improving the blackness of the cured film, rhodamine-based acid dyes containing CI Acid Red 52 are even more preferred.
[0107] Basic dyes are compounds or their salts containing basic groups such as amino and imino groups, which are cationic dyes in aqueous solutions. Among these, basic dyes containing triarylmethane-based basic dyes are preferred for improving the blackness of the cured film. For further improvement in the blackness of the cured film, triarylmethane-based basic dyes are more preferably those containing Basic Blue 7 (CI) and / or Basic Blue 26 (CI).
[0108] Salts of acid and basic dyes can be synthesized using known methods. For example, aqueous solutions of acid and basic dyes are prepared separately, and then slowly mixed while stirring. As a precipitate, a salt of the acid and basic dyes is formed. This salt can be recovered by filtration. The obtained salt is preferably dried at approximately 60–70°C.
[0109] Furthermore, by making the content of the salt-forming compound in the photosensitive resin composition 10 parts by weight or more relative to 100 parts by weight of the alkali-soluble resin (A), blackening can be achieved, and by making it 75 parts by weight or less, residue at the opening can be reduced. By containing the salt-forming compound within this range, the alkali solubility of the exposed portion, the unexposed portion, and the halftone exposed portion described later can be appropriately adjusted.
[0110] In addition, if it is desired to improve the blackness of the cured film, it is preferable to use a (D) coloring material containing (D3-2) nonionic dyes.
[0111] (D3-2) Nonionic dyes are dyes other than acid dyes and basic dyes, and refer to dyes that do not have an ionic structure.
[0112] Examples of nonionic dyes include: CI Disperse Orange 5; CI Disperse Red 58; CI Disperse Blue 165; CI Solvent Red 18, etc., which are azo-based nonionic dyes; CI Vat Blue 4; CI Disperse Red 22, 60; CI Disperse Violet 26, 28, 31; CI Disperse Blue 14, 56, 60; CI Solvent Violet 13, 31, 36; CI Solvent Blue 35, 36, 45, 63, 78, 87, 97, 104, 122, etc., which are anthraquinone-based nonionic dyes.
[0113] Among them, anthraquinone-based nonionic dyes are preferred from the perspective of improving the blackness of the cured film.
[0114] <(D1) Organic Pigments>
[0115] Regarding (D1) organic pigments used as (D) coloring materials, examples include phthalocyanine pigments, anthraquinone pigments, quinacridone pigments, pinanthrone pigments, dioxazine pigments, thioindigo pigments, pyrrolopyrroledione pigments, quinoline yellow pigments, reduction pigments, indoline pigments, isoindoline pigments, isoindolineone pigments, benzofuranone pigments, perylene pigments, aniline pigments, azo pigments, azomethyl alkali pigments, condensed azo pigments, carbon black, metal complex pigments, lake pigments, toner pigments, or fluorescent pigments. From the viewpoint of heat resistance, anthraquinone pigments, quinacridone pigments, pinanthrone pigments, pyrrolopyrroledione pigments, benzofuranone pigments, perylene pigments, condensed azo pigments, and carbon black are preferred.
[0116] In this invention, considering the effect of imparting light-blocking properties to the pixel segmentation layer, the photosensitive resin composition used to form the pixel segmentation layer preferably contains organic pigments. By containing organic pigments in the photosensitive resin composition, the pixel segmentation layer becomes a layer containing organic pigments, achieving the effects described below, which is therefore preferred. In this case, it is preferable to further contain organic black pigments and / or mixed-color organic black pigments (hereinafter, sometimes referred to as component (b)) as (D1) organic pigments.
[0117] Examples of organic black pigments include benzodifuranone-based black pigments, perylene-based black pigments, and azomethyl alkali-based black pigments.
[0118] As a benzodifuranone-based black pigment, for example, the pigment disclosed in International Publication No. 2009 / 010521 can be cited. As a commercially available benzodifuranone-based black pigment formed from the compound represented by formula (5) described below, Irgaphor Black (registered trademark) S0100CF and Experimental Black 582 (both manufactured by BASF) are preferred.
[0119] Examples of perylene-based black pigments include CI Pigment Black 31, CI Pigment Black 32, benzimidazole perylenetetracarboxylate or its derivatives, and the pigments disclosed in International Publication No. 2005 / 078023. Commercially available products may include Spectrasense Black S0084 (registered trademark), Spectrasense Black L0086, Spectrasense Black K0087, and Spectrasense Black K0088 (all manufactured by BASF).
[0120] As an azomethyl alkali-based black pigment, for example, the pigment disclosed in U.S. Patent Application Publication No. 2002-121228 can be cited. As a commercially available product, Chromofine Black A1103 (manufactured by Daihatsu Seika Co., Ltd.) can be used.
[0121] A mixed organic black pigment refers to a pigment mixture containing (b-1) an organic pigment of at least one color selected from organic yellow pigment, organic red pigment and organic orange pigment (hereinafter, sometimes referred to as component (b-1)) and (b-2) an organic pigment of at least one color selected from organic blue pigment and organic purple pigment (hereinafter, sometimes referred to as component (b-2)), and the content of component (b-2) is 20% by weight or more relative to the total amount of component (b-1) and component (b-2).
[0122] Examples of organic yellow pigments include CI Pigment Yellow 24, 120, 138, 139, 151, 175, 180, 185, 181, 192, 193, and 194. Examples of organic orange pigments include CI Pigment Orange 13, 36, 43, 60, 61, 62, 64, 71, and 72. Examples of organic red pigments include CI Pigment Red 122, 123, 149, 178, 177, 179, 180, 189, 190, 202, 209, 254, 255, and 264. Examples of organic blue pigments include CI Pigment Blue 15, 15:1, 15:2, 15:3, 15:6, 16, 25, 56, 57, 60, 61, 64, 65, 66, 75, 79, and 80. Examples of organic purple pigments include CI pigments 19, 23, 29, 32, and 37.
[0123] Of the components belonging to component (b) above, from the perspective of reducing brightness unevenness, the component (b) contained in the pixel dividing layer of the organic EL display device of the present invention preferably contains an organic black pigment, and the organic black pigment contains a compound represented by formula (5) or formula (6) and / or its isomers. The component (b) contained in the pixel dividing layer more preferably contains a compound represented by formula (7) or its isomers. The compounds represented by formulas (5) to (7) can be synthesized and pigmented by reacting 2,5-dihydroxy-1,4-phenylenediacetic acid with indigo or its derivatives under an acidic catalyst.
[0124] [Chemical Formula 3]
[0125]
[0126] [Chemical Formula 4]
[0127]
[0128] In equations (5) and (6), R 22 1 ~R 31 10 Each can be independently represented by an alkyl group having 1 to 12 hydrogen atoms or carbon atoms.
[0129] [Chemical Formula 5]
[0130]
[0131] From the perspective of further suppressing uneven brightness, the component belonging to component (b) can be a substance obtained by micronization using known methods such as solvent salt milling or acid paste method. When micronizing benzodifuranone-based black pigments, uneven brightness can sometimes be easily suppressed by having the compound represented by formula (8) or its salt coexist and adsorb onto the pigment surface.
[0132] [Chemical Formula 6]
[0133]
[0134] In equation (8), n and m represent integers, each being 0 to 2 independently.
[0135] Among them, n+m≥1 is satisfied.
[0136] Furthermore, in the case where component (b) contains a benzodifuranone-based black pigment, in order to improve developability and suppress development residue at the opening, it is preferable that the pigment surface has a coating layer containing silica. The silica contained in the coating layer referred to herein is not component (a) as described above, but rather constitutes a part of component (b).
[0137] Regarding the content of component (b), from the perspective of exhibiting high light-blocking properties, it is preferably 1% by weight or more, more preferably 10% by weight or more, in the pixel segmentation layer. From the perspective of reducing brightness unevenness, it is preferably 50% by weight or less, more preferably 30% by weight or less.
[0138] Furthermore, when component (a) is present in addition to component (b), from the perspective of reducing brightness unevenness, the content of component (a) relative to 100 parts by weight of component (b), calculated in terms of SiO2, is preferably 20 to 70 parts by weight, more preferably 30 to 50 parts by weight. That is, in the organic EL display device of the present invention, in the pixel segmentation layer, the content of the aforementioned component (a) relative to component (b), calculated in terms of SiO2, is preferably 20 to 70 parts by weight.
[0139] <(E)Lithophobic Materials>
[0140] When forming an organic EL layer using inkjet printing, the photosensitive resin composition used in this invention preferably contains a hydrophobic material. Known substances such as fluorinated polymers and fluorinated compounds containing silane compounds can be used, but hydrophobic materials having at least amide or urethane groups are preferred. By having amide or urethane groups, compatibility with the aforementioned alkali-soluble resin (A) is improved, resulting in reduced defects such as pinholes and improved uniformity of the cured film thickness. Consequently, display defects in the display device are reduced.
[0141] Examples of hydrophobic materials include 2-(perfluorobutyl)ethyl methacrylate and 2-(perfluorohexyl)ethyl methacrylate, which are (meth)acrylate monomers containing perfluoroalkyl groups; and commercially available products such as "Megaface (registered trademark)" RS-72-K, RS-72-A, RS-75, RS-76-E, RS-76-NS, RS-78, and RS-90 (manufactured by DIC Corporation).
[0142] In addition, preferred examples of (meth)acrylate monomers containing epoxy groups include glycidyl acrylate, glycidyl methacrylate, 4-hydroxybutyl acrylate glycidyl ether (4-HBAGE), 4-hydroxybutyl methacrylate glycidyl ether, acrylates having alicyclic epoxy groups, and methacrylates having alicyclic epoxy groups.
[0143] Liquid-repellent materials (E) having amide or urethane groups can also be copolymers obtained by further substituting different functional groups into (meth)acrylic acid monomers. By substituting different functional groups into (meth)acrylic acid monomers, a balance between liquid repellency and solubility can be easily obtained. Examples include hydroxyl-containing (meth)acrylates, hydroxyl-containing (meth)acrylamides, alkoxy-containing (meth)acrylates, (meth)acrylates with terminal isocyanate groups, phenoxy-containing (meth)acrylates, alkyl (meth)acrylates, and vinyl-containing compounds. Examples of hydroxyl-containing (meth)acrylates include 2-hydroxyethyl (meth)acrylate. Examples of hydroxyl-containing (meth)acrylamides include N-hydroxymethylacrylamide. Examples of alkoxy-containing (meth)acrylates include 3-methacryloyloxypropylmethyldimethoxysilane. Examples of (meth)acrylates containing capped isocyanate groups include 2-(O-[1'-methylpropyleneamino]carboxyamino)ethyl methacrylate (Karenz MOI-BM: manufactured by Showa Denko Co., Ltd.; registered trademark). Examples of (meth)acrylates containing phenoxy groups include 2-phenoxybenzyl acrylate and 3-phenoxybenzyl acrylate. Alkyl (meth)acrylates are unsubstituted or substituted (meth)acrylate diluent monomers of unsubstituted or substituted alkyl (meth)acrylates having 1 to 12 carbon atoms, which may be substituted by at least one of amino, monoalkylamino, dialkylamino, hydrocarbon aromatic ring, or heterocyclic ring, or by anhydride cleavage addition to a hydroxyl group; examples include alkyl acrylates. Examples of vinyl compounds include n-butyl vinyl ether.
[0144] The compounds contained in the liquephobic material (E) having amide or urethane groups are typically copolymers. Copolymers containing compounds in the liquephobic material (E) can be obtained using known polymerization methods. For example, copolymers can be obtained through ionic polymerization such as free radical polymerization or anionic polymerization. Alternatively, they can be any of random copolymers, block copolymers, grafted copolymers, or alternating copolymers. Here, free radical copolymerization is cited as an example. The liquephobic material (E) can be obtained by randomly copolymerizing, for example, a specified amount of dimethacrylamide, a specified amount of fluorinated methacrylate monomers, and, as needed, specified amounts of epoxy-containing methacrylates, hydroxyl-containing methacrylates, hydroxyl-containing methacrylamides, alkoxy-containing methacrylates, isocyanate-terminated methacrylates, phenoxy-containing methacrylates, alkyl methacrylates, or vinyl-containing compounds with a free radical polymerization initiator in a suitable solvent. During random copolymerization, chain transfer agents can be added as needed. For example, tert-butyl peroxide-2-ethylhexanoate can be used as a free radical polymerization initiator. For example, dodecyl mercaptan can be used as a chain transfer agent. Additionally, inert solvents such as cyclohexanone can be used as a solvent.
[0145] The weight-average molecular weight of the hydrophobic material (E) having amide or urethane groups is preferably in the range of 1,500 to 50,000. By having a molecular weight within this range, it is easier to dissolve in the solvent used in the photosensitive resin composition. Furthermore, by having a molecular weight within this range, the defoaming properties of the photosensitive resin composition solution are improved, which is therefore preferable. From the viewpoint that the resulting cured film easily exhibits sufficient hydrophobicity, the hydrophobic material (E) having amide or urethane groups is preferably 0.1 parts by weight or more, more preferably 0.3 parts by weight or more, relative to 100 parts by weight of the alkali-soluble resin (A). Furthermore, from the viewpoint that it is less likely to generate hydrophobicity within the pixel and that high durability is easily obtained, it is preferably 10 parts by weight or less, more preferably 5 parts by weight or less.
[0146] <spacer>
[0147] In the organic EL display device of the present invention, spacers 4 are disposed on the pixel segmentation layer. As a first objective, by providing spacers, the contact area between the substrate and the vapor deposition mask during the formation of the organic EL layer can be reduced, thereby suppressing particle generation during the process. As a result, it is possible to suppress the reduction in panel yield and the deterioration of the light-emitting elements. Furthermore, as a second objective, as mentioned above, spacers need to be fabricated on the pixel segmentation layer in order to support the structure covering the second electrode in subsequent processes and ensure the strength of the display device. Like the pixel segmentation layer, the spacers must be patterned; residue from the removal process can sometimes directly lead to defects such as short circuits and black spots. In addition, the shape of the edge of the spacer can become a cause of breakage in the second electrode, therefore a smooth, tapered shape or similar processability is required.
[0148] As a spacer, any material with the required mechanical and electrical properties can be used without particular limitation, and is not limited to any known organic or inorganic material. From a processability perspective, a cured film of a photosensitive resin composition is preferred. Furthermore, by forming the same material as the pixel dividing layer in a single process, it is possible to increase the yield of the panel, shorten the processing time, and reduce costs.
[0149] As mentioned earlier, the problem of delamination between the pixel segmentation layer and the organic EL layer also becomes a problem at the interface where the spacer and the organic EL layer meet. Therefore, in this invention, when the maximum value of the surface roughness (Ra1) of the pixel segmentation layer and the surface roughness (Ra2) of the spacer is set as Ramax, Ramax is 1.0 nm or more and 50 nm or less. Furthermore, it is more preferable that the surface roughness (Ra2) of the spacer is Ramax. Alternatively, both the surface roughness (Ra1) of the pixel segmentation layer and the surface roughness (Ra2) of the spacer can be Ramax. It should be noted that the surface roughness of the spacer can also be measured using atomic force microscopy (AFM) in the same way as that of the pixel segmentation layer.
[0150] Furthermore, since the spacer is formed on the outermost surface of the substrate, the surface of the spacer becomes the interface with the organic EL layer. Conventionally, poor adhesion between the spacer and the organic EL layer has led to easy delamination, a significant problem, especially in flexible products. In this invention, by making the surface roughness (Ra2) of the spacer 1.0 nm or more, an anchoring effect can be obtained; preferably 5.0 nm or more, more preferably 20 nm or more, improves the adhesion with the organic EL layer. Regarding the surface roughness (Ra2) of the spacer, if it is 1.0 nm or more, an anchoring effect can be obtained; for the purpose of suppressing pinholes in the second electrode and defects in the sealing process described later, it is preferable to make it 50 nm or less. Furthermore, when improving adhesion through a large Ra2, it is effective to ensure that the interface between the spacer and the organic EL layer is as large as possible. When Ra2 is greater than the surface roughness Ra1 of the aforementioned pixel segmentation layer, i.e., Ra2 becomes Ramax, the area of the interface between the spacer and the organic EL layer is preferably 50% or more of the total area of the interface between the substrate and the organic EL layer. This means that the spacer is 50% or more of the surface area of the substrate.
[0151] When Ra1 and Ra2 are greater than 1.0 nm, in addition to the improved adhesion, it is also possible to suppress external light reflection from the display device by increasing the diffuse reflection of the substrate. Normally, when external light is incident on the substrate, two types of reflected light are generated on the substrate surface: direct reflection and diffuse reflection. The total amount of reflected light is the sum of these two types, but direct reflection has a greater impact on human perception, causing glare or reflections. Therefore, increasing the diffuse reflection of the substrate and reducing direct reflection is effective in ensuring the display quality of the display device. Specifically, by increasing the surface roughness (Ra1, Ra2) of the pixel segmentation layer and spacers on the substrate surface to 1.0 nm or greater, the diffuse reflection at the substrate surface is increased, thereby ensuring the display quality of the display device.
[0152] Furthermore, when the absolute value of the difference between Ra1 and Ra2 is greater than 1.0 nm, two anchoring effects are obtained, and the tightness is improved, so it is more preferable.
[0153] Furthermore, the shape of the spacer's edge can cause the second electrode to break, so a gentle, positive cone shape is preferred. Here, a positive cone shape refers to a state where the angle formed by the tangent at the interface between the pixel segmentation layer and the spacer, and the tangent at a position on the surface of the cone-shaped portion of the spacer where the maximum thickness of the spacer is 50% of the film thickness, is less than 90 degrees.
[0154] The thickness of the spacer is typically 0.3 μm to 10 μm, as long as it is sufficient to contact the vapor deposition mask and support the structure covering the second electrode; there are no particular limitations.
[0155] <Organic EL Layer>
[0156] In the organic EL display device of the present invention, the composition of the organic EL layer 5 is not particularly limited. For example, it can be any of (1) a hole transport layer / light-emitting layer, (2) a hole transport layer / light-emitting layer / electron transport layer, or (3) a light-emitting layer / electron transport layer. Alternatively, it can be a series-connected type formed by stacking multiple of the above-described compositions with a charge-generating layer between them. The charge-generating layer is also commonly referred to as an electron extraction layer, a connecting layer, an intermediate layer, an intermediate electrode, an intermediate conductive layer, or an intermediate insulating layer, and can be constructed using known materials. By arranging it in a series-connected type, improved luminous brightness and luminous lifetime are expected, and therefore it is preferred. Specific examples of series-connected structures include (4) hole transport layer / light emission layer / electron transport layer / charge generation layer / hole transport layer / light emission layer / electron transport layer, (5) hole injection layer / hole transport layer / light emission layer / electron transport layer / electron injection layer / charge generation layer / hole injection layer / hole transport layer / light emission layer / electron transport layer / electron injection layer, and (6) hole transport layer / light emission layer / electron transport layer / charge generation layer / hole transport layer / light emission layer / electron transport layer / charge generation layer / hole transport layer / light emission layer / electron transport layer, which are stacked structures containing a charge generation layer between the anode and the cathode.
[0157] Furthermore, each of the aforementioned layers can be a single layer, any of multiple layers, and can be doped. In particular, the electron transport layer and charge generation layer are preferably metal-doped layers, which improve electron transport capability and the ability to inject electrons into adjacent layers. In addition to the aforementioned layers, a protective layer (capping layer) may also be provided, which can further improve luminous efficiency through optical interference effects. Considering the influence on the resistivity of each layer material and the extraction efficiency of EL emission, the thickness of each layer is typically selected between 1 and 200 nm.
[0158] <Hole transport layer>
[0159] Hole transport layers can be formed, for example, by layering or mixing one or more hole transport materials, or by using a mixture of hole transport materials and polymeric binders. Alternatively, inorganic salts such as ferric chloride (III) can be added to the hole transport materials to form a hole transport layer. The hole transport material is not particularly limited as long as it is a compound capable of forming a thin film required for manufacturing a light-emitting element, injecting holes from an electrode that serves as the anode, and thus transporting holes. The hole transport layer can be a single layer or composed of multiple layers.
[0160] Preferred examples of hole transport materials include triphenylamine derivatives such as 4,4'-bis(N-(3-methylphenyl)-N-phenylamino)biphenyl, 4,4'-bis(N-(1-naphthyl)-N-phenylamino)biphenyl, and 4,4',4”-tris(3-methylphenyl(phenyl)amino)triphenylamine, bis(N-allylcarbazole) and other biscarbazole derivatives, pyrazoline derivatives, brunzide compounds, hydrazone compounds, benzofuran derivatives, thiophene derivatives, oxadiazole derivatives, phthalocyanine derivatives, porphyrin derivatives and other heterocyclic compounds, as well as polycarbonates, styrene derivatives, polythiophene, polyaniline, polyfluorene, polyvinylcarbazole and polysilanes having the aforementioned monomers in the side chain in the polymer system.
[0161] <Emitting Layer>
[0162] In the light-emitting layer, injected electrons recombine with holes to emit light. A key feature of organic EL displays is their ability to produce a wide variety of multi-color emission by selecting the materials that constitute this light-emitting layer.
[0163] The luminescent layer is a layer that emits light by exciting the luminescent material through the recombination energy generated by the collision of holes and electrons. The luminescent layer can be a single layer or composed of multiple stacked layers, each formed by a luminescent material (a host material and / or a dopant material). Each luminescent layer can be composed of only one of the host material or the dopant material, or it can be composed of a combination of one or more host materials and one or more dopant materials. That is, in each luminescent layer, only the host material or the dopant material can emit light, or both the host material and the dopant material can emit light. From the viewpoint of efficient use of electrical energy and obtaining high color purity luminescence, the luminescent layer is preferably composed of a combination of host material and dopant material. The dopant material can be included in the entire host material or in a part of the host material.
[0164] From the viewpoint of suppressing concentration extinction phenomenon, the content of doped material in the light-emitting layer is preferably 30 parts by weight or less, more preferably 20 parts by weight or less, relative to 100 parts by weight of the host material.
[0165] The light-emitting layer can be formed by methods such as co-evaporation of the host material and the dopant material; pre-mixing the host material and the dopant material before evaporation; and so on.
[0166] Examples of main materials constituting luminescent materials include naphthalene, anthracene, phenanthrene, and pyrene. Compounds with fused aromatic rings, such as tetraphenylene, triphenylene, perylene, fluoranthene, fluorene, and indene, are preferred. Two or more of these compounds may be used. As the host material used for triplet luminescence (phosphorescence) in the luminescent layer, metal-chelated oxinoid compounds, dibenzofuran derivatives, dibenzothiophene derivatives, carbazole derivatives, indolocarbazole derivatives, triazine derivatives, and triphenylene derivatives are preferred. Compounds with an anthracene or pyrene skeleton are more likely to achieve high-efficiency luminescence and are therefore preferred.
[0167] Examples of dopant materials constituting luminescent materials include, for example, fused-ring derivatives such as anthracene and pyrene; metal complex compounds such as tris(8-hydroxyquinoline)aluminum; bis(styrene) derivatives such as bis(styrene)anthracene derivatives and styrenebenzene derivatives; tetraphenylbutadiene derivatives; dibenzofuran derivatives; carbazole derivatives; indolocarbazole derivatives; polyphenylene ethylene derivatives; and so on. When used as a dopant material for triplet luminescence (phosphorescence) in the luminescent layer, metal complex compounds containing at least one metal selected from the group consisting of iridium (Ir), ruthenium (Ru), palladium (Pd), platinum (Pt), osmium (Os), and rhenium (Re) are preferred. The ligands constituting the metal complex compounds can be appropriately selected based on the desired luminescence color, the performance of the organic EL display device, and its relationship with the host compound; nitrogen-containing aromatic heterocycles such as phenylpyridine skeletons, phenylquinoline skeletons, and carbene skeletons are preferred. Specifically, examples include tris(2-phenylpyridinyl)iridium complex, bis(2-phenylpyridinyl)(acetylacetone)iridium complex, and tetraethylporphyrin platinum complex. Two or more of these can be used.
[0168] <Electron transport layer>
[0169] The electron transport layer is the layer that transports electrons injected from the cathode to the light-emitting layer. To achieve a low driving voltage, the organic EL layer of the present invention preferably also includes an electron transport layer. Regarding the electron transport layer, it is desirable to have high electron injection efficiency and efficient transport of injected electrons. Therefore, the electron transport layer is preferably made of a material with high electron affinity and electron mobility, excellent stability, and is not prone to the formation of traps during manufacturing and use. Especially when the film thickness is large, low molecular weight compounds are prone to crystallization and other defects that degrade the film quality; therefore, compounds with a molecular weight of 400 or higher are preferred. It should be noted that, considering the balance between hole and electron transport, the electron transport layer is also preferably capable of efficiently preventing unrecombined holes from flowing from the anode to the cathode side. In the electron transport layer of the present invention, a hole-blocking layer, which effectively prevents hole movement, is also included as a layer with the same meaning. The electron transport layer can be a single layer or a multilayer structure.
[0170] Examples of electron transport materials constituting the electron transport layer include fused polycyclic aromatic derivatives such as naphthalene and anthracene. Two or more of these can be used. Among these, compounds having a heteroaromatic ring structure containing electron-accepting nitrogen are preferred from the perspective of further reducing the driving voltage and obtaining high-efficiency luminescence.
[0171] The electron-accepting nitrogen referred to here means a nitrogen atom forming multiple bonds between adjacent atoms. Because nitrogen atoms have high electronegativity, these multiple bonds have the property of accepting electrons. Therefore, aromatic heterocycles containing electron-accepting nitrogen have high electron affinity. Electron transport materials with electron-accepting nitrogen readily accept electrons from cathodes with high electron affinity, thus further reducing the driving voltage. Furthermore, the increased supply of electrons to the luminescent layer and the higher recombination probability result in improved luminous efficiency.
[0172] Examples of heteroaromatic rings containing electron-accepting nitrogen include triazine rings and pyridine rings. From the viewpoint of electron transport capability, compounds having these heteroaromatic ring structures are preferably triazole derivatives such as N-naphthyl-2,5-diphenyl-1,3,4-triazole, bipyridine derivatives such as 2,5-bis(6'-(2',2”-bipyridinyl))-1,1-dimethyl-3,4-diphenylthiophene, and tripyridine derivatives such as 1,3-bis(4'-(2,2':6'2”-tripyridinyl))benzene. Two or more of these can be used.
[0173] Furthermore, compounds having a phenanthroline skeleton can be cited as examples of substances that meet the requirements of the electron transport layer. To obtain stable luminescence over a long period, materials with excellent thermal stability and thin film forming properties are desired. Among compounds having a phenanthroline skeleton, compounds in which the substituent itself has a three-dimensional structure, or compounds that have a three-dimensional structure through steric repulsion with the phenanthroline skeleton or with adjacent substituents, or compounds linking multiple phenanthroline skeletons are preferred. Moreover, when multiple phenanthroline skeletons are linked, compounds in which the linking unit includes a conjugated bond, a substituted or unsubstituted aromatic hydrocarbon, or a substituted or unsubstituted aromatic heterocycle are more preferred.
[0174] The electron transport material is not limited to a single compound with a phenanthroline skeleton; multiple of the aforementioned compounds can be used in combination, or one or more known electron transport materials can be mixed with the aforementioned compounds. Known electron transport materials are not particularly limited and include quinoline alcohol derivative metal complexes (represented by 8-hydroxyquinoline aluminum), benzoquinoline metal complexes, cycloheptatrienone metal complexes, flavonol metal complexes, perylene derivatives, pyrene derivatives, naphthalene, coumarin derivatives, oxadiazole derivatives, aldehyde azo derivatives, bis(styrene) derivatives, pyrazine derivatives, phenanthroline derivatives, quinoline derivatives, benzimidazole derivatives, triazole derivatives, quinoxaline derivatives, benzoquinoline derivatives, etc., without particular limitation. These electron transport materials can be used alone or layered or mixed with different electron transport materials. Additionally, compounds with nitrogen-containing aromatic heterocycles, such as phenanthroline derivatives and oligopyridine derivatives, can also be used. In particular, compounds with a phenanthroline skeleton, described later, exhibit excellent electron transport capabilities and are therefore preferred.
[0175] The aforementioned electron transport materials can be used alone, or two or more of the aforementioned electron transport materials can be mixed together, or one or more other electron transport materials can be mixed with the aforementioned electron transport materials. Furthermore, the electron transport layer in this invention preferably includes a donor-doped material. Here, a donor-doped material refers to a compound that improves the electron injection barrier, facilitating electron injection from the cathode or electron injection layer to the electron transport layer, thereby increasing the conductivity of the electron transport layer. In this invention, the donor-doped material preferably contains one or more substances selected from the group consisting of alkali metals, alkaline earth metals, rare earth metals, inorganic salts of such metals, and complexes of such metals with organic compounds. Regarding the donor-doped material, from the perspective of ease of vacuum deposition and excellent operation, inorganic salts or complexes with organic compounds are preferred over elemental metals; from the perspective of ease of operation in the atmosphere and ease of adjusting the addition concentration, complexes with organic compounds are more preferred.
[0176] <charge generation layer>
[0177] The charge generation layer typically comprises two layers. Specifically, a pn-junction type charge generation layer comprising an n-type charge generation layer and a p-type charge generation layer can be used. This pn-junction type charge generation layer generates charge by applying a voltage to the organic EL layer, or by separating the charge into holes and electrons, which are then injected into the light-emitting layer via a hole transport layer and an electron transport layer. Specifically, the charge generation layer functions as an intermediate layer among multiple light-emitting layers in the organic EL layer. The n-type charge generation layer supplies electrons to the light-emitting layer on the anode side, and the p-type charge generation layer supplies holes to the light-emitting layer on the cathode side. Therefore, the luminous brightness and luminous efficiency of the organic EL layer comprising multiple light-emitting layers are further improved, the driving voltage can be reduced, and the luminous lifetime of the organic EL layer can be further increased. For these reasons, in this invention, the organic EL layer preferably comprises a charge generation layer. Furthermore, as described below, in this invention, the charge generation layer preferably comprises a donor-doped material, which preferably contains one or more selected from the group consisting of alkali metals, alkaline earth metals, rare earth metals, inorganic salts of such metals, and complexes of such metals with organic compounds.
[0178] The aforementioned n-type charge generation layer preferably comprises an n-type dopant material and a host material, which can be made of known materials. For example, alkali metals, alkaline earth metals, or rare earth metals can be used as the n-type dopant material. Additionally, compounds with nitrogen-containing aromatic heterocycles, such as compounds with a phenanthroline backbone and oligopyridine derivatives, can be used as the host material. In particular, the compounds with a phenanthroline backbone described later exhibit excellent properties as host materials for the aforementioned n-type charge generation layer; therefore, it is preferable to use them in combination.
[0179] The aforementioned p-type charge generation layer preferably comprises a p-type dopant material and a host material, which can be known materials. For example, as a p-type dopant material, tetrafluorene-7,7,8,8-tetracyanoquinone dimethane (F4-TCNQ), tetracyanoquinone dimethane derivatives, axialene derivatives, iodine, FeCl3, FeF3, SbCl5, etc., can be used. Axylene derivatives are preferred as p-type dopant materials. Arylamine derivatives are preferred as host materials.
[0180] <Compounds with a phenanthrene skeleton>
[0181] In this invention, the electron transport layer and / or charge generation layer preferably comprises a compound having a phenanthroline skeleton represented by the following general formula (1).
[0182] [Chemical Formula 7]
[0183]
[0184] Here, R1 to R8 can be the same or different, and are selected from hydrogen atoms, alkyl groups, cycloalkyl groups, alkenyl groups, cycloalkenyl groups, aryl groups, heteroaryl groups, and heterocyclic groups. Among them, at least one of R1, R3, R6, and R8 is selected from adamantyl, norbornel, phenyl vinyl, β-naphthyl, phenanthryl, and pyrene.
[0185] Furthermore, in this invention, the electron transport layer and / or charge generation layer more preferably comprises a compound having a phenanthroline skeleton represented by the following general formula (2).
[0186] [Chemical Formula 8]
[0187]
[0188] Here, R9~R 16 Each can be the same or different, and can be selected from hydrogen atoms, alkyl groups, cycloalkyl groups, alkenyl groups, cycloalkenyl groups, aryl groups, heteroaryl groups, heterocyclic groups, and X1. Among them, R9 to R 16 At least one of them is X1. n represents a natural number from 2 to 6. X1 is a single bond, or an n-valent linking unit that connects multiple phenanthroline skeletons, derived from any of benzene, anthracene, pyridine, ethylene, thiophene, furan, methylene, carbazole, cyclohexane, spirodifluorene, triphenylamine, triptene, and structures formed by combining them.
[0189] Among these substituents, alkyl groups represent, for example, saturated aliphatic hydrocarbon groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, and tert-butyl, which may or may not have substituents. There are no particular limitations on the additional substituents in the case of substitution; for example, alkyl, halogen, aryl, and heteroaryl groups can be mentioned, and this will be consistent throughout the following description. Furthermore, the number of carbon atoms in the alkyl group is not particularly limited; from the perspective of ease of acquisition and cost, a range of 1 to 20 is preferred, and a range of 1 to 8 is more preferred. Additionally, cycloalkyl groups represent, for example, saturated alicyclic hydrocarbon groups such as cyclopropyl, cyclohexyl, norbornenealkyl, and adamantyl, which may or may not have substituents. The number of carbon atoms in the alkyl moiety is not particularly limited, but a range of 3 to 20 is preferred. Furthermore, aralkyl groups represent, for example, aromatic hydrocarbon groups derived from aliphatic hydrocarbons such as benzyl and phenylethyl; both aliphatic and aromatic hydrocarbons may be unsubstituted or substituted. Additionally, alkenyl refers to unsaturated aliphatic hydrocarbon groups containing double bonds, such as vinyl, allyl, and butadienyl, which may be unsubstituted or substituted. Cycloalkenyl refers to unsaturated alicyclic hydrocarbon groups containing double bonds, such as cyclopentenyl, cyclopentadienyl, and cyclohexenyl, which may be unsubstituted or substituted. Alkynyl refers to unsaturated aliphatic hydrocarbon groups containing triple bonds, such as ethynyl, which may be unsubstituted or substituted. Alkoxy refers to aliphatic hydrocarbon groups formed by ether bonds, such as methoxy, which may be unsubstituted or substituted. Alkylthio refers to a group obtained by replacing the oxygen atom in the ether bond of an alkoxy group with a sulfur atom. Arylether refers to aromatic hydrocarbon groups formed by ether bonds, such as phenoxy, which may be unsubstituted or substituted. Arylthioether refers to a group obtained by replacing the oxygen atom in the ether bond of an aryl ether group with a sulfur atom. Furthermore, aryl refers to aromatic hydrocarbon groups such as phenyl, naphthyl, biphenyl, phenanthryl, terphenyl, and pyrene, which may be unsubstituted or substituted. Heterocyclic groups refer to aliphatic rings such as pyran rings, piperidine rings, and cyclic amides, which have atoms other than carbon atoms within the ring, and may or may not have substituents. The number of carbon atoms in heterocyclic groups is not particularly limited, but is preferably in the range of 2 to 20. Halogens refer to fluorine, chlorine, bromine, and iodine. Halogenated alkanes, halogenated alkenes, and halogenated alkynes refer to groups obtained by substituting part or all of the aforementioned alkyl, alkenyl, or alkyne groups, such as trifluoromethyl, with the remaining portion may be unsubstituted or substituted. Aldehyde groups, carbonyl groups, ester groups, carbamoyl groups, and amino groups also include groups substituted by aliphatic hydrocarbons, alicyclic hydrocarbons, aromatic hydrocarbons, or heterocycles; furthermore, aliphatic hydrocarbons, alicyclic hydrocarbons, aromatic hydrocarbons, and heterocycles may be unsubstituted or substituted. Silyl refers to silicon compound groups such as trimethylsilyl, which may be unsubstituted or substituted. Siloxane refers to silicon compound groups such as trimethylsiloxane, which are formed by ether bonds and may be unsubstituted or substituted.Additionally, ring structures can be formed between adjacent substituents. The formed ring structures can be unsubstituted or substituted.
[0190] Furthermore, the substituent itself possesses a three-dimensional structure, or forms a three-dimensional structure through steric repulsion with the phenanthroline skeleton or adjacent substituents. Therefore, compounds containing the phenanthroline skeleton have low planarity, are less prone to crystallization, and can maintain a good amorphous film state. Substituents possessing a three-dimensional structure include, for example, tert-butyl, adamantyl, norbornene, which are not two-dimensional planar structures and have large volumes; they can be unsubstituted or substituted. Substituents that form a three-dimensional structure through steric repulsion with the phenanthroline skeleton or adjacent substituents include α-naphthyl, phenanthryl, mesitylene, etc. Although the substituent itself has a planar structure, through steric repulsion between the substituent and the phenanthroline skeleton, or between the substituent and adjacent substituents, the plane of the substituent lies in a plane different from the plane of the phenanthroline skeleton. These cases can be examined using molecular models, computational chemistry, etc.
[0191] Furthermore, by linking multiple phenanthroline skeletons, compounds containing phenanthroline skeletons can be increased in molecular weight, resulting in an increased glass transition temperature. They are still not prone to crystallization and can maintain a good amorphous film state.
[0192] In the compounds of general formula (1) of the present invention having a phenanthroline skeleton, it is further preferred that substituents are introduced at positions 2, 4, 7, and 9 of the phenanthroline skeleton. These substituents are the same as those for the groups described above. Specifically, but not limited to, the structures described above for compounds having a phenanthroline skeleton are as follows.
[0193] [Chemical Formula 9]
[0194]
[0195] [Chemical Formula 10]
[0196]
[0197] [Chemical Formula 11]
[0198]
[0199] [Chemical Formula 12]
[0200]
[0201] The host material for the electron transport layer and / or charge generation layer is not limited to a single compound with a phenanthroline skeleton; multiple compounds with phenanthroline skeletons can be mixed and used, or one or more known host materials can be mixed with a compound with a phenanthroline skeleton. There are no particular limitations on known host materials; previously known anthracene, phenanthrene, pyrene, perylene, etc., can be used. Metal complexes of quinolinol derivatives, represented by tris(8-hydroxyquinoline)aluminum, benzoxazole derivatives, piracetam derivatives, benzothiazole derivatives, thiadiazole derivatives, thiophene derivatives, tetraphenylbutadiene derivatives, cyclopentadiene derivatives, oxadiazole derivatives, bis(styrene)-anthracene derivatives, styrene-phenylene derivatives, etc., bis(styrene)-phenylene derivatives, metal complexes obtained by combining quinolinol derivatives with different ligands, oxadiazole derivative metal complexes, benzoxazole derivative metal complexes, coumarin derivatives, pyrrolopyridine derivatives, pyrenone derivatives, thiadiazole-pyridine derivatives, polyphenylene ethylene derivatives in polymer systems, poly(p-phenylene) derivatives, and polythiophene derivatives, etc.
[0202] In addition, although compounds with a phenanthroline skeleton can also be used as dopants, they are preferred as host materials due to their excellent electron transport capabilities.
[0203] <Second Electrode>
[0204] In this invention, the second electrode 6, in the case of bottom-emitting type, needs to be a light-reflective electrode, and in the case of top-emitting type, needs to be a light-transmitting electrode.
[0205] For bottom-emitting types, materials exhibiting high visible light reflectivity and low electrical resistance at a certain film thickness or greater are preferred. Ag or Ag alloy films containing Ag as the main component have high reflectivity and are therefore useful. Ag alloy films can use MgAg alloys, etc., with Ag as the main component. In addition, Al or Al alloy films containing Al as the main component are also good as second electrodes for bottom-emitting applications. AlCr alloy films containing Cr and AlNi alloy films containing Ni have high reflectivity comparable to pure Al and can achieve low electrical resistance, and are therefore preferred.
[0206] For top-emitting types, transparent conductive metal oxides such as tin oxide, indium oxide, and indium tin oxide (ITO) can be used. In order to avoid damage to the organic EL layer, a thin film of MgAg alloy that can be fabricated by vapor deposition is preferred.
[0207] Similar to the first electrode, the resistance of the second electrode is not limited as long as it can provide sufficient current for the light-emitting element to emit light. From the viewpoint of power consumption of the light-emitting element, low resistance is preferred. The thickness of the electrode can be arbitrarily selected according to characteristics such as transmittance and resistance. For bottom-emitting type, it can be used in the range of 100 to 300 nm, and for top-emitting type, it can be used in the range of 10 to 30 nm.
[0208] Wiring, TFT
[0209] In this invention, as described above, sometimes wiring, TFT7 and other driving circuits are provided as components included in the substrate 1.
[0210] In the case of an organic EL display device that is an active-drive top-emitting type, it is common for the first electrode 2, which is patterned into an island shape, to be connected to the TFT 7, which is formed as part of the substrate 1.
[0211] Examples of semiconductor layers for TFTs include a-Si (amorphous silicon), p-Si (polycrystalline silicon), microcrystalline silicon, oxides such as In-Ga-Zn-O, and LTPO (Low Temperature Polycrystalline Oxide), which combines p-Si with oxides. A-Si TFTs and p-Si TFTs are commonly used. A-Si TFTs have low electron mobility, an indicator of electron mobility, and a relatively short manufacturing process, allowing for fabrication on large substrates, making them widely applicable to small to large displays. P-Si TFTs, on the other hand, have higher mobility, allowing for the formation of driving circuits on the substrate. However, their manufacturing process is longer than a-Si, and fabrication on large substrates is more difficult, making them primarily suitable for small to medium-sized displays. In particular, the p-Si layer in p-Si TFTs is typically formed by irradiating a-Si as a starting film with a laser, causing it to melt and crystallize instantaneously. In addition, there are doping processes that are not used in the manufacturing process of a-Si TFTs, such as the doping of phosphorus and boron into Si. The threshold of TFT characteristics can also be controlled by doping impurities into the Si film.
[0212] TFTs can be broadly categorized structurally into bottom-gate and top-gate types. a-Si TFTs are preferably bottom-gate, while p-Si TFTs are preferably top-gate. For example, in a top-gate type, the semiconductor layer is connected to the drain-side electrode and the source-side electrode, and a gate electrode is positioned above the semiconductor layer. The TFT is formed on the substrate by repeating the steps of thin film formation, patterning, etching, and cleaning several times. Known methods can be used to form the TFT. Conversely, in a bottom-gate type, the gate electrode is positioned at the bottom layer, a semiconductor layer / insulating film is positioned above it, and then the source and drain electrodes are formed on top of that. A structure known as an "anti-interlaced structure" can be formed, where the gate electrode is connected to the source and drain electrodes in a straight line, creating an inverted triangle.
[0213] <Planning Layer>
[0214] Especially for active drive types, such as... Figure 2 As shown, when wiring and TFT7 are provided inside the substrate 1, a planarization layer 8 is preferably used. By providing the planarization layer 8, the unevenness of the wiring and TFT7 can be covered and planarized. In this case, since the first electrode 2 is provided on the planarization layer, it is preferable that the first electrode 2 and the wiring and TFT7 are connected through contact holes formed in the planarization layer 8. The planarization layer 8 is not limited to any known organic or inorganic material, and from a processability perspective, a cured film containing a photosensitive resin composition is preferred. As for the planarization layer 8, for example, a thin film can be uniformly formed on a large substrate, so it can be coated using wet coating methods such as spin coating, slot coating, dip coating, spray coating, and printing.
[0215] The photosensitive resin composition preferably contains (A) an alkali-soluble resin, (B) a photosensitizer, and (C) an organic solvent, and may also contain (D) a coloring material. As a photosensitive resin composition, the combination of (A) an alkali-soluble resin and (B) a photosensitizer allows for pattern processing using photosensitivity. Furthermore, by containing (C) an organic solvent, a varnish-like state can be formed, which may improve coatability. In addition, by including (D) a coloring material in the photosensitive resin composition, the planarization layer can be blackened. The photosensitive resin composition may also contain other components.
[0216] Materials for (A) alkali-soluble resins include, for example, acrylic resins, epoxy resins, polyamide resins, silicone resins, and precursors of these resins. The film thickness is only required to cover the unevenness and is not particularly limited. When coloring is necessary from the viewpoint of light-shielding and anti-reflection, it is preferable to include a suitable coloring material.
[0217] <Sealing layer>
[0218] After the second electrode is formed, preferably, for example, as shown in the figure Figure 5 As shown, sealing is achieved through sealing layer 9. This is because the light-emitting elements of organic EL (organic EL) are weakly resistant to oxygen and moisture; therefore, sealing in an atmosphere with minimal oxygen and moisture is preferable for obtaining a highly reliable display device. Regarding the components used in sealing layer 9, components with high gas barrier properties are preferred, and similarly to the substrate 1, appropriate materials such as glass, resin film, and gas barrier film can be selected. For example, materials such as SiO2 (silicon oxide), SiN (silicon nitride), and SiON (silicon oxynitride) can be used as gas barrier films. Alternatively, sealing layer 9, formed of resin materials such as acrylic resin or silicone resin, can be provided on top of a layer formed using materials such as SiO2 (silicon oxide), SiN (silicon nitride), or SiON (silicon oxynitride). In the case of a top-emitting display device, a light-transmitting material is preferred.
[0219] In addition, when bonding is required, the adhesive used should be a material with high gas barrier properties. Commonly known materials such as two-component epoxy adhesive (XNR, manufactured by Nagase ChemteX Co., Ltd.) and organic device sealing material (MOISTURE CUT, manufactured by MORESCO Co., Ltd.) can be selected. Alternatively, a method of melting sintered glass with a laser in the periphery of the display device can be used.
[0220] Furthermore, considering moisture content, introducing a desiccant during the sealing process is also effective. Known desiccants include barium oxide and calcium oxide; any desiccant with high moisture adsorption capacity is acceptable, and there are no particular limitations.
[0221] <Polarizing layer>
[0222] For example, Figure 5 As shown, the organic EL display device of the present invention preferably further includes a polarizing layer 10. Specifically, a linear polarizing layer and a λ / 4 phase retardation layer are stacked to suppress the reflection of light incident on the display device from the outside. The linear polarizing layer is not particularly limited; for example, a film obtained by dyeing a polyvinyl alcohol-based film with iodine and then uniaxially stretching it is commonly used. The material constituting the λ / 4 phase retardation layer is not particularly limited; a heat-resistant polyimide-based resin or the like is preferred.
[0223] <Ultraviolet Absorption Layer>
[0224] For example, Figure 5As shown, the organic EL display device of the present invention preferably includes an ultraviolet absorption layer 11. By including the ultraviolet absorption layer 11, the degradation of the substrate and the organic EL layer 5 caused by ultraviolet light can be suppressed, thereby improving the reliability of the display device. As the ultraviolet absorption layer 11, it is preferably a layer that absorbs light with a wavelength of 320 nm or less, more preferably a layer that absorbs light with a wavelength of 360 nm or less, and even more preferably a layer that absorbs light with a wavelength of 420 nm or less. However, light with a wavelength of 420 nm or more overlaps with the blue emission wavelength used for display, therefore the ultraviolet absorption layer 11 preferably has high transmittance in the region with a wavelength of 420 nm or more. This is particularly effective when using the organic EL display device of the present invention outdoors.
[0225] The ultraviolet absorbing layer 11 preferably contains resins such as polyimide resin, polyamide resin, polyamide-imide resin, polycarbonate resin, polyester resin, polyethersulfone resin, polyarylate resin, polyolefin resin, polyethylene terephthalate resin, polymethyl methacrylate resin, polysulfone resin, polyethylene resin, polyvinyl chloride resin, alicyclic olefin polymer resin, acrylic polymer resin, and cellulose ester resin. It may contain two or more of these. Among these, polyimide resin and polyamide resin are more preferred.
[0226] The 11th ultraviolet absorbing layer may contain an ultraviolet absorber. Examples of ultraviolet absorbers include benzophenone compounds, oxybenzophenone compounds, benzotriazole compounds, salicylates, salicylates, acrylonitrile compounds, cyanoacrylate compounds, hindered amine compounds, triazine compounds, nickel complex salt compounds, ultrafine titanium dioxide, metal complex salt compounds, and other known polymeric ultraviolet absorbers. Two or more of these may be present. For excellent transparency, benzotriazole compounds and benzophenone compounds are preferred, and benzotriazole compounds are more preferably preferred.
[0227] As a polymeric ultraviolet absorber, for example, an ultraviolet absorber obtained by copolymerizing the reactive ultraviolet absorber RUVA-93 manufactured by Otsuka Chemical Co., Ltd. with an acrylic monomer can be cited.
[0228] <Manufacturing Method of Organic EL Display Device>
[0229] The method for manufacturing an organic EL display device of the present invention is a method for manufacturing an organic EL display device having a substrate, an organic EL layer 5 and a second electrode 6. The substrate has a first electrode 2, a pixel segmentation layer 3 and a spacer 4 on a substrate 1. The method includes a step of processing the pixel segmentation layer 3 and the spacer 4 together. The photomask used for processing together is a halftone photomask having a light-transmitting part, a light-blocking part and a semi-light-transmitting part.
[0230] An example of the manufacturing method of the organic EL display device of the present invention is as follows: [The method involves] manufacturing... Figure 5 The following explanation will be based on the case of a top-emitting organic EL display device.
[0231] First, wiring and TFTs 7 are formed on a substrate that serves as a resin film. As a process, in addition to TFT formation processes such as "gate electrode formation process", "gate insulating film formation process", "Si film formation process", and "source electrode and drain electrode formation process", wiring for ensuring electrical connection is also provided, all of which can be formed using known methods.
[0232] Next, a planarization layer 8 is coated using a slot coating method to form a film, which is then heated and cured. Contact holes are pre-formed for connection with the first electrode 2. If the material used for the planarization layer 8 is photosensitive, photolithography can be used; if it is non-photosensitive, conventional etching using a resist material as a mask can be used. In this way, the substrate 1 is completed.
[0233] Next, on the substrate, as the first electrode 2, AgPdCu and ITO are sequentially deposited into films and patterned to form the first electrode 2.
[0234] In the method for manufacturing the organic EL display device of the present invention, a pixel segmentation layer 3 is formed in the gap of the first electrode 2, and then a spacer 4 is formed on the pixel segmentation layer. As a step, after coating the entire surface with photosensitive resin, an opening is formed on the first electrode by photolithography, and the opening becomes a display pixel.
[0235] In the manufacturing method of the organic EL display device of the present invention, the steps of forming the pixel segmentation layer 3 and forming the spacer 4 on the pixel segmentation layer are performed in a combined manner. The photomask used for simultaneously processing the pixel segmentation layer 3 and the spacer 4 needs to be a halftone photomask having a light-transmitting portion, a light-blocking portion, and a semi-transparent portion. Normally, in the case of processing utilizing photosensitivity, a full-tone photomask consisting of a light-blocking portion and a light-transmitting portion is used. However, the halftone photomask used in the present invention refers to the following photomask: for example, Figure 6Thus, in addition to the pattern including the light-transmitting portion 12 and the light-shielding portion 14, a semi-transparent portion 13 with a transmittance lower than that of the light-transmitting portion 12 and a transmittance higher than that of the light-shielding portion 14 is also present between the light-transmitting portion 12 and the light-shielding portion 14. By using a halftone mask for exposure, a pattern with a stepped shape can be formed after development and heat curing. It should be noted that when the photosensitive resin composition is positive, the exposed portion irradiated with active chemical rays through the aforementioned light-transmitting portion is alkali-soluble and becomes an opening, while the unexposed portion that is not irradiated with active chemical rays through the aforementioned light-shielding portion becomes a thick film, equivalent to the spacer 4, and the halftone exposed portion irradiated with active chemical rays through the aforementioned semi-transparent portion is equivalent to the aforementioned pixel segmentation layer 3 with a film thickness less than that of the spacer 4. Conversely, when the photosensitive resin composition is negative, the cured portion irradiated with active chemical rays through the aforementioned light-transmitting portion is equivalent to the aforementioned spacer 4, and the halftone exposed portion irradiated with active chemical rays through the aforementioned semi-transparent portion is equivalent to the aforementioned pixel segmentation layer 3.
[0236] As described below, the transmittance of the semi-transparent portion of the halftone mask used in this invention is preferably 15% to 50% of the transmittance of the transparent portion. When the transmittance of the transparent portion is set to (%TFT), the transmittance (%THT) of the semi-transparent portion is preferably 15% or more (%TFT), and more preferably 20% or more. If the transmittance (%THT) of the semi-transparent portion is within the above range, the exposure amount during the formation of the solidified pattern with a stepped shape can be reduced, thereby shortening the takt time. On the other hand, the transmittance (%THT) of the semi-transparent portion is preferably 50% or less (%TFT), and more preferably 45% or less. If the transmittance (%THT) of the semi-transparent portion is within the above range, the thickness difference between the spacer 4 and the pixel dividing layer 3 can be sufficiently increased, improving the reliability of the display device. Furthermore, if the transmittance of the semi-transparent portion is within the aforementioned range, during the patterning process of the photosensitive resin composition, insufficient exposure to reactive chemical rays will occur in the semi-transparent portion. Following the development process after irradiation by the reactive chemical rays, a difference in surface roughness will arise between the pixel dividing layer 3 and the spacer 4. In this way, by setting a difference in the absolute value of the difference between the surface roughness Ra1 of the pixel dividing layer 3 and the surface roughness Ra2 of the spacer 4, two anchoring effects are obtained as described above, thereby improving adhesion. To effectively obtain the anchoring effect, the difference between Ra1 and Ra2 is preferably ensured to be 1.0 nm or more. Besides the transmittance of the semi-transparent portion, Ra1 and Ra2 can also be adjusted by modifying the resin composition, including the presence of coloring materials, hydrophobic materials, etc.
[0237] In addition to the process of using halftone photomasks mentioned above, several methods such as mechanical grinding with abrasive materials, shot peening with abrasive materials, wet sandblasting, plasma treatment, and dry etching treatment such as RIE can be combined to adjust the surface roughness. In this invention, in order to make the absolute value of the difference between Ra1 and Ra2 greater than 1.0 nm, halftone photomasks must be used.
[0238] In the method for manufacturing the organic EL display device of the present invention, a cleaning step may be performed before the step of forming the organic EL layer 5, which will be described later. Typically, contaminants from previous processes such as photolithography often remain on the surface of the first electrode, so wet or dry cleaning is effective. For wet cleaning, organic solvents, surfactants, water, acids, alkalis, etc., can be used, and methods such as immersion cleaning, ultrasonic cleaning, and boiling cleaning can be selected. For dry cleaning, methods such as glow discharge treatment, plasma discharge treatment, and UV / ozone treatment can be selected. Dry cleaning using an oxygen atmosphere can remove contaminants and adjust the work function. By adjusting the characteristics of the first electrode 2, the efficiency of carrier injection from the first electrode 2 to the adjacent organic EL layer 5 is increased, resulting in improved luminous efficiency, reliability, and other characteristics of the display device.
[0239] Next, the method for manufacturing the organic EL display device of the present invention includes a step of forming an organic EL layer 5. Each layer constituting the organic EL layer 5, such as the hole transport layer, the light-emitting layer, and the electron transport layer, can be formed using known methods, for example, by mask evaporation or inkjet printing.
[0240] Mask evaporation refers to a method of patterning organic compounds by evaporating them using an evaporation mask. For example, a method involves placing an evaporation mask with the desired pattern as an opening on the evaporation source side of a substrate for evaporation. To obtain high-precision evaporation patterns, it is important to ensure a tight seal between the evaporation mask and the substrate with high flatness. Common techniques include applying tension to the evaporation mask or using a magnet positioned on the back of the substrate to ensure a tight seal. However, the generation of particles due to the contact between the substrate and the evaporation mask can lead to a decrease in panel yield and degradation of the light-emitting elements. Therefore, it is preferable to minimize the size and number of spacers 4 in contact with the evaporation mask.
[0241] Methods for manufacturing vapor deposition masks include etching, mechanical grinding, sandblasting, sintering, laser processing, the use of photosensitive resins, and electroforming. When fine patterns are required, etching and electroforming, which have excellent processing precision, are preferred.
[0242] For mask evaporation and inkjet printing methods, the more intricate the pattern, the greater the difficulty. Therefore, it is required, for example, to use a minimum amount of light-emitting layer that determines the color of the emitted light. In this case, by sharing different colors for hole transport layers, electron transport layers, etc., other than the light-emitting layer, it is possible to form a film on the entire surface, thereby increasing the yield of the panel and reducing the cost.
[0243] The method for manufacturing the organic EL display device of the present invention further includes a step of forming a second electrode 6. Known methods can be used for this formation, but vacuum evaporation is preferred because it easily avoids deterioration or damage to the organic EL layer 5 that serves as the substrate.
[0244] In manufacturing Figure 5 In the method for constructing an organic EL display device, after the step of forming the second electrode 6, a sealing layer 9, a polarizing layer 10, and an ultraviolet absorption layer 11 are sequentially stacked. Each layer can be formed using known methods, and the process is completed as described above. Figure 5 Organic EL display device.
[0245] Example
[0246] The present invention will be described below by way of examples, but the present invention is not limited to these examples.
[0247] In the following evaluations, for those where the number of trials n is not recorded, n=1 will be used for evaluation.
[0248] <Film thickness measurement of pixel segmentation layer and spacer, conical observation>
[0249] Regarding the film thickness of the pixel segmentation layer and spacers in each embodiment and comparative example, the difference in thickness between the pixel segmentation layer and spacers on the patterned substrate (100mm × 100mm) was measured using a surface roughness measuring machine (SURFCOM 1400D, Tokyo Seimitsu Co., Ltd.). Regarding the conical shape, a cross-section obtained by cutting the patterned substrate was observed using a scanning electron microscope (SEM, S-3000N, Hitachi High-Technologies Co., Ltd.).
[0250] <Surface roughness of pixel segmentation layer and spacer>
[0251] Regarding the surface roughness of the pixel separation layer and spacers in each embodiment and comparative example, an atomic force microscope (AFM, Dimension Icon, Bruker) was used to observe the pixel separation layer and spacers on a patterned substrate (100mm × 100mm). The results are presented as arithmetic mean roughness (Ra). The observation conditions were set as follows: RTESP-300 probe, tapping mode, scan size 5μm□, scan rate 0.1Hz, and 1024 sampling lines.
[0252] <Observation of silica particles contained in pixel segmentation layers>
[0253] Regarding the silica particles contained in the pixel segmentation layer in each embodiment and comparative example, an image analysis particle size distribution measuring machine (Mac-View, manufactured by MOUNTECH) was used to measure the particle size distribution in images obtained by transmission electron microscopy-energy dispersive X-ray spectroscopy (TEM-EDX) at a magnification of 50,000x. Specifically, in a cross-section of the pixel segmentation layer on a patterned substrate (100mm × 100mm), silica particles were randomly selected from 30 TEM images (experiment number n = 30). For each particle, the major axis, minor axis, and aspect ratio in the TEM image were measured. Silica particles with a major axis (nm) of 5–30 nm and an aspect ratio in the range of 1.0–1.5 were defined as component (a). It should be noted that for a single silica particle, if the minor axis and major axis are equal in the TEM image (i.e., a perfect circle), its diameter is considered the major axis. As representative values representing the characteristics of silica particles belonging to component (a), the average value of the first particle size, i.e. the average value of the major diameter, is calculated, and the value obtained by rounding the first decimal place is calculated, as well as the average value of the aspect ratio, i.e. the average value of the aspect ratio of each silica particle belonging to component (a), and the value obtained by rounding the second decimal place is used.
[0254] For the presence or absence of component (a) in each embodiment and comparative example, the presence of component (a) is set as A, and the absence of component (a) is set as B. The cross-sectional analysis results of embodiments 23, 24, and 25 in Table 10 that contain component (a) are shown in Table 11.
[0255] <Measurement of Diffuse Reflection Light>
[0256] Regarding the measurement of diffuse reflectance of the substrates in each embodiment and comparative example, a spectrophotometer (CM-2600d, manufactured by KONICA MINOLTA JAPAN) was used to measure the diffuse reflectance of a patterned substrate (100mm × 100mm) on the surface where the pixel separation layer and spacers are formed. The diffuse reflectance at a wavelength of 550nm was used in the SCE mode to remove positively reflected light. The higher the diffuse reflectance, the better it can suppress positively reflected light, and the better the characteristics are judged.
[0257] <Seamless Test>
[0258] Regarding the sealing test of the organic EL display devices in each embodiment and comparative example, such as Figure 7As shown, a 5mm diameter metal cylinder is fixed to the center of the side opposite to the surface where the light-emitting element is formed on a substrate (100mm × 100mm) with a light-emitting element. The cylinder is repeatedly bent within a range from 0° (when the substrate is flat) to 180° (when the cylinder is folded back). The bent portion is then observed using an optical microscope. Delamination occurring after 1 to 100 bends indicates low adhesion (characteristic C); delamination occurring after 101 to 1000 bends indicates characteristic B; and delamination occurring after 1001 bends or more indicates high adhesion (characteristic A). It should be noted that the test was performed 10 times (test n = 10), and the result with the fewest bends until delamination occurred was used.
[0259] <Weather Resistance Reliability Test>
[0260] Regarding the weathering reliability test of the organic EL display devices in each embodiment and comparative example, the appearance of the organic EL display devices manufactured in each embodiment and comparative example described below after being placed at room temperature of 23°C and 45% humidity for 24 hours was confirmed. In the test, 10 display devices were put in (test number n was 10). If no corrosion was observed in the second electrode, the weathering reliability was considered good and was judged as (A). Even if corrosion was observed in one of them, it was considered that there was a pinhole in the second electrode and was judged as (B).
[0261] <Electrical Reliability Test>
[0262] Regarding the electrical reliability test of the organic EL display devices in the various embodiments and comparative examples, in the organic EL display devices manufactured in the embodiments and comparative examples described below, the current value when a 5V voltage is applied between two adjacent strip-shaped first electrodes was measured. During the measurement, a digital source meter (2400, manufactured by Keithley Instruments Co., Ltd.) was used. The smaller the current value, the less the leakage current, and the better the characteristic. It should be noted that the test was conducted at 20 locations (test n = 20), and the average of 10 measurements after removing 5 values of each magnitude was used.
[0263] <Luminous Properties Test>
[0264] Regarding the light emission characteristics tests of the organic EL display devices in the various embodiments and comparative examples, in the organic EL display devices fabricated in the embodiments and comparative examples described later, a current of 10 mA / cm² flowed through one light-emitting element with a selected pair of crossed first and second electrodes. 2The voltage and brightness were measured at the current. For voltage measurement, a digital source meter (2400, Keithley Instruments, Inc.) was used; for brightness measurement, a spectroradiometer (CS-1000, KONICA MINOLTA) was used.
[0265] <Design of the first electrode and halftone photomask>
[0266] The designs of the first electrode and halftone mask in each embodiment and comparative example are shown below. Figure 6 .like Figure 6 As shown in diagram a, 100 first electrodes 2, each with a linewidth of 60 μm, a spacing of 100 μm, and a length of 10 mm, are fabricated in a strip shape at the center of substrate 1 (100 mm × 100 mm). That is, the exposed portion of substrate 1 is 40 μm wide. In contrast, for the positive halftone mask b, the linewidths are adjusted with a spacing of 100 μm, using the light-blocking portion 14 as a spacer and the semi-transparent portion 13 as a pixel segmentation layer. For the negative halftone mask c, the linewidths I and II are adjusted, using the light-transmitting portion 12 as a spacer and the semi-transparent portion 13 as a pixel segmentation layer. In all cases, the pixel segmentation layer and spacers are arranged in the gaps between the first electrodes as shown in diagram a. Figure 6 This alignment is performed. In the completed substrate, linewidth I corresponds to the interface between the pixel segmentation layer and the organic EL layer, and linewidth II corresponds to the interface between the spacer and the organic EL layer.
[0267] <Preparation of Photosensitive Resin Compositions>
[0268] The photosensitive resin compositions R-1 to R-15 used in the various examples and comparative examples were prepared as follows. It should be noted that compounds used with abbreviations will have their names shown below.
[0269] BAHF: 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane
[0270] BFE: 1,2-bis(4-formylphenyl)ethane
[0271] BIP-PHBZ: 4,4',4”-Methylenetriphenol (manufactured by Asahi Organic Materials Co., Ltd.)
[0272] BYK-333: A silicone-based surfactant, "BYK" (registered trademark) 333 (manufactured by BYK-Chemie).
[0273] DAE: Diaminodiphenyl ether
[0274] DFA: N,N-dimethylformamide dimethyl acetal
[0275] DMAA: N,N-dimethylacrylamide
[0276] DPCA-60: Caprolactone 6-molar modified dipentaerythritol hexaacrylate (a hexafunctional acrylate with 6 pentylene oxygen chains, manufactured by Nippon Kayaku Co., Ltd.)
[0277] EL: Ethyl lactate
[0278] FAMAC-6: 2-(perfluorohexyl)ethyl methacrylate
[0279] GBL: γ-Butyrolactone
[0280] GMA: Glycidyl methacrylate
[0281] HA: a diamine compound containing a hydroxyl group
[0282] HMOM-TPHAP: A compound with the following chemical formula (manufactured by Honshu Chemical Industry Co., Ltd.) having a phenolic hydroxyl group and substituents with a molecular weight of 40 or more at the two adjacent positions of the phenolic hydroxyl group.
[0283] [Chemical Formula 13]
[0284]
[0285] KBM-403: 3-Epoxypropoxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd.)
[0286] MAP: 3-Aminophenol; m-Aminophenol
[0287] MBA: 3-Methoxybutyl Acetate
[0288] MEK-ST-40: Silica particle dispersion (manufactured by Nissan Chemical Industries, Ltd.). The solvent is methyl ethyl ketone.
[0289] MEK-ST-L: Silica particle dispersion (manufactured by Nissan Chemical Industries, Ltd.). The solvent is methyl ethyl ketone.
[0290] MeTMS: Methyltrimethoxysilane
[0291] NA: 5-norbornene-2,3-dicarboxylic anhydride; Nadic anhydride
[0292] TMOS: Tetramethoxysilane
[0293] NCI-831: "Adeka Arkls" (registered trademark) NCI-831 (manufactured by ADEKA Co., Ltd.)
[0294] NMP: N-methyl-2-pyrrolidone
[0295] ODPA: Bis(3,4-dicarboxyphenyl) ether dianhydride; Oxybis(phthalic acid) dianhydride
[0296] OSCAL-1421: Silica particle dispersion (manufactured by Nippon Gas Chemical Industry Co., Ltd.). Solvent type: isopropanol.
[0297] PGME: Propylene Glycol Monomethyl Ether
[0298] PGMEA: Propylene glycol monomethyl ether acetate
[0299] PhTMS: Phenylacetyltrimethoxysilane
[0300] S0100CF: Irgaphor Black (registered trademark) S0100CF
[0301] SiDA: 1,3-bis(3-aminopropyl)tetramethyldisiloxane
[0302] S-20000: "SOLSPERSE" (registered trademark) 20000 (polyether dispersant, manufactured by Lubrizol)
[0303] TMSSucA: 3-Trimethoxysilylpropylsuccinic anhydride
[0304] TrisP-PA: 1,1-bis(4-hydroxyphenyl)-1-[4-[1-(4-hydroxyphenyl)-1-methylethyl]phenyl]ethane (manufactured by Honshu Chemical Industry Co., Ltd.)
[0305] WR-301: “ADEKA ARKLS” (registered trademark) WR-301 (manufactured by ADEKA Co., Ltd.)
[0306] Karenz MOI-BM: 2-(O-[1'-methylpropyleneamino]carboxyamino)ethyl methacrylate
[0307] Bisphenol AF: 2,2-bis(4-hydroxyphenyl)hexafluoropropane (manufactured by Central Glass Co., Ltd.)
[0308] 6FDA: 2,2-(3,4-dicarboxyphenyl)hexafluoropropane dianhydride; 4,4'-hexafluoropropane-2,2-diyl-bis(1,2-phthalic anhydride)
[0309] Pigment dispersant 1: Pigment dispersant 1 (solid component 100% by weight) disclosed in Synthesis Example 2 of Japanese Patent Application Publication No. 2020 / 70352. It is a polymeric dispersant having a linear polyalkylene amine structure and a polyether-based polymer chain.
[0310] <Synthesis Example 1: Synthesis of Polyimide Resin (PI-1)>
[0311] Under a dry nitrogen stream, in a three-necked flask, weigh and dissolve 31.13 g (0.085 mol; 77.3 mol% relative to structural units derived from all amines and their derivatives), 1.24 g (0.0050 mol; 4.5 mol% relative to structural units derived from all amines and their derivatives), 2.18 g (0.020 mol; 18.2 mol% relative to structural units derived from all amines and their derivatives), MAP as a capping agent, and 150.00 g of NMP. Add to this a solution obtained by dissolving 31.02 g (0.10 mol; 100 mol% relative to structural units derived from all carboxylic acids and their derivatives) of ODPA in 50.00 g of NMP, and stir at 20°C for 1 hour, followed by stirring at 50°C for 4 hours. Then, add 15 g of xylene, and while azeotropically mixing water and xylene, stir at 150°C for 5 hours. After the reaction was complete, the reaction solution was added to 3 L of water, filtered, and a solid precipitate was obtained. The obtained solid was washed three times with water and then dried in a vacuum dryer at 80 °C for 24 hours to obtain polyimide resin (PI-1). The obtained polyimide resin (PI-1) had a weight-average molecular weight (Mw) of 27,000 and an acid equivalent of 350.
[0312] <Synthetic Example 2: Synthesis of HA>
[0313] Weigh 18.31 g (0.05 mol) of BAHF, 17.42 g (0.3 mol) of propylene oxide, and 100 mL of acetone into a three-necked flask and dissolve them. Add dropwise a solution obtained by dissolving 20.41 g (0.11 mol) of 3-nitrobenzoyl chloride in 10 mL of acetone. After the addition is complete, react at -15 °C for 4 hours, then return to room temperature. Filter out the precipitated white solid and dry under vacuum at 50 °C. Place 30 g of the resulting solid into a 300 mL stainless steel autoclave and disperse it in 250 mL of 2-methoxyethanol, adding 2 g of 5% palladium-carbon. Introduce hydrogen into the autoclave using a balloon and react at room temperature for 2 hours. After 2 hours, confirm that the balloon no longer deflates. After the reaction is complete, filter to remove the palladium compound acting as a catalyst, and concentrate by vacuum distillation to obtain a hydroxyl-containing diamine compound (HA) with the following structure.
[0314] [Chemical Formula 14]
[0315]
[0316] <Synthesis Example 3: Synthesis of Polyimide Precursor Resin (PIP-1)>
[0317] Under a dry nitrogen stream, in a three-necked flask, 44.42 g (0.10 mol; 100 mol% relative to structural units derived from all carboxylic acids and their derivatives) of 6FDA and 150 g of NMP were weighed and dissolved. A solution obtained by dissolving 14.65 g (0.040 mol; 32.0 mol% relative to structural units derived from all amines and their derivatives) of BAHF, 18.14 g (0.030 mol; 24.0 mol% relative to structural units derived from all amines and their derivatives) of HA, and 1.24 g (0.0050 mol; 4.0 mol% relative to structural units derived from all amines and their derivatives) of SiDA in 50 g of NMP was added, and the mixture was stirred at 20 °C for 1 hour, followed by stirring at 50 °C for 2 hours. Next, a solution obtained by dissolving 5.46 g (0.050 mol; 40.0 mol% relative to structural units derived from all amines and their derivatives) of MAP as a capping agent in 15 g of NMP was added, and the mixture was stirred at 50 °C for 2 hours. Then, a solution obtained by dissolving 23.83 g (0.20 mol) of DFA in 15 g of NMP was added. After the addition was complete, the mixture was stirred at 50 °C for 3 hours. After the reaction was complete, the reaction solution was cooled to room temperature, and then added to 3 L of water. The solution was filtered to obtain a precipitated solid. The solid was washed three times with water and then dried in a vacuum dryer at 80 °C for 24 hours to obtain polyimide precursor resin (PIP-1). The obtained polyimide precursor resin (PIP-1) had a weight-average molecular weight (Mw) of 20,000 and an acid equivalent of 450.
[0318] <Synthesis Example 4: Synthesis of Polyimide Precursor Resin (PIP-2)>
[0319] Under a dry nitrogen stream, 21.2 g (0.035 mol) of HA, 7.0 g (0.035 mol) of DAE, and 1.2 g (0.005 mol) of SiDA obtained in Synthesis Example 2 were dissolved in 400 g of NMP. Then, 31.0 g (0.10 mol) of ODPA was added to the solution along with 50 g of NMP, and the mixture was stirred at 40 °C for 1 hour. Next, 5.5 g (0.050 mol) of MAP was added, and the mixture was stirred at 40 °C for 1 hour. Then, a solution containing 8.3 g (0.07 mol) of DFA dissolved in 10 g of NMP was added. After the addition was complete, the mixture was stirred at 40 °C for 3 hours. After stirring, the solution was cooled to room temperature and then added to 3 L of water, yielding a white precipitate. The precipitate was collected by filtration, washed three times with water, and dried in a vacuum dryer at 50°C for 72 hours to obtain an alkali-soluble resin (PIP-2) containing a polyimide precursor resin with an acid equivalent of 275 g / mol.
[0320] <Synthesis Example 5: Synthesis of Polyimide Precursor Resin (PIP-3)>
[0321] The amount of DFA added using the same method as in Synthesis Example 4 was 13.1 g (0.11 mol), thereby obtaining an alkali-soluble resin (PIP-3) containing a polyimide precursor resin with an acid equivalent of 329 g / mol.
[0322] <Synthesis Example 6: Synthesis of Polyimide Precursor Resin (PIP-4)>
[0323] The amount of DFA added using the same method as in Synthesis Example 4 was 16.7 g (0.14 mol), thereby obtaining an alkali-soluble resin (PIP-4) containing a polyimide precursor resin with an acid equivalent of 366 g / mol.
[0324] <Synthesis Example 7: Synthesis of Polybenzoxazole Resin (PBO-1)>
[0325] In a 500 mL round-bottom flask equipped with a Dean-Stark water separator filled with toluene and a condenser, 34.79 g (0.095 mol; 95.0 mol% relative to structural units derived from all amines and their derivatives), 1.24 g (0.0050 mol; 5.0 mol% relative to structural units derived from all amines and their derivatives), and 75.00 g of NMP were weighed and dissolved. A solution was then added to which 19.06 g (0.080 mol; 66.7 mol% relative to structural units derived from all carboxylic acids and their derivatives) of BFE and 6.57 g (0.040 mol; 33.3 mol% relative to structural units derived from all carboxylic acids and their derivatives) of NA as a capping agent were dissolved. The solution was stirred at 20 °C for 1 hour, followed by stirring at 50 °C for 1 hour. Then, under a nitrogen atmosphere, the mixture was heated and stirred at above 200 °C for 10 hours to carry out a dehydration reaction. After the reaction was complete, the reaction solution was added to 3 L of water, filtered, and a solid precipitate was obtained. The solid was washed three times with water and then dried in a vacuum dryer at 80 °C for 24 hours to obtain polybenzoxazole resin (PBO-1). The obtained polybenzoxazole resin (PBO-1) had a weight-average molecular weight (Mw) of 25,000 and an acid equivalent of 330.
[0326] <Synthetic Example 8: Synthesis of Polybenzoxazole Precursor Resin (PBOP-1)>
[0327] In a 500 mL round-bottom flask equipped with a Dean-Stark water separator filled with toluene and a condenser, 34.79 g (0.095 mol; 95.0 mol% relative to structural units derived from all amines and their derivatives), 1.24 g (0.0050 mol; 5.0 mol% relative to structural units derived from all amines and their derivatives), and 70.00 g of NMP were weighed and dissolved. A solution obtained by dissolving 19.06 g (0.080 mol; 66.7 mol% relative to structural units derived from all carboxylic acids and their derivatives) of BFE in 20.00 g of NMP was added, and the mixture was stirred at 20 °C for 1 hour, followed by stirring at 50 °C for 2 hours.
[0328] Next, a solution was obtained by dissolving 6.57 g (0.040 mol; 33.3 mol%) of NA as a capping agent in 10 g of NMP, and the mixture was stirred at 50 °C for 2 hours. Then, under a nitrogen atmosphere, the mixture was stirred at 100 °C for 2 hours. After the reaction was complete, the reaction solution was added to 3 L of water, filtered, and a solid precipitate was obtained. The solid was washed three times with water and dried in a vacuum dryer at 80 °C for 24 hours to obtain polybenzoxazole precursor resin (PBOP-1). The obtained polybenzoxazole precursor resin (PBOP-1) had a weight-average molecular weight (Mw) of 20,000 and an acid equivalent of 330.
[0329] <Synthesis Example 9: Synthesis of Polysiloxane Resin Solution (PS-1)>
[0330] A three-necked flask was filled with 23.84 g (35 mol%) of MeTMS, 49.57 g (50 mol%) of PhTMS, 3.81 g (5 mol%) of TMOS, and 76.36 g of PGMEA. Air was introduced into the flask at a rate of 0.05 L / min, and the mixture was heated to 40 °C in an oil bath while stirring. While continuing to stir the mixture, an aqueous solution of phosphoric acid (0.271 g dissolved in 28.38 g of water) was added dropwise over 10 minutes. After the addition was complete, the mixture was stirred at 40 °C for 30 minutes to hydrolyze the silane compounds. After hydrolysis, a solution of 13.12 g (10 mol%) of TMSucA (13.12 g dissolved in 8.48 g of PGMEA) was added. Then, the bath temperature was set to 70 °C and stirred for 1 hour, followed by raising the temperature to 115 °C. After heating begins, the internal temperature of the solution reaches 100°C after approximately one hour. From this point, heating and stirring are carried out for 2 hours (internal temperature 100–110°C). The resulting resin solution, obtained after 2 hours of heating and stirring, is cooled in an ice bath. Anion exchange resin and cation exchange resin are then added separately at 2% by weight relative to the resin solution, and the mixture is stirred for 12 hours. After stirring, the anion exchange resin and cation exchange resin are removed by filtration, yielding a polysiloxane resin solution (PS-1). The obtained polysiloxane resin has a weight-average molecular weight (Mw) of 4,200 and a carboxylic acid equivalent (acid equivalent) of 700 g / mol.
[0331] <Synthetic Example 10: Synthesis of the photosensitizer (quinone diazide compound b-1)>
[0332] Under a dry nitrogen stream, 21.22 g (0.05 mol) of TrisP-PA (trade name, manufactured by Honshu Chemical Industry Co., Ltd.) and 36.27 g (0.135 mol) of 5-naphthoquinone diazidesulfonyl chloride were dissolved in 450 g of 1,4-dioxane and placed at room temperature. 15.18 g of triethylamine, mixed with 50 g of 1,4-dioxane, was added dropwise to the system in a manner that prevented the system temperature from exceeding 35°C. The mixture was stirred at 30°C for 2 hours after the addition. The triethylamine salt was filtered, and the filtrate was added to water. The precipitate was then collected by filtration. The precipitate was dried using a vacuum dryer to obtain a photosensitizer (quinone diazide compound b-1) with the following structure.
[0333] [Chemical Formula 15]
[0334]
[0335] <Preparation of salt-forming compound d-1>
[0336] 9.25 g (0.018 mol) of Basic Blue 7 (CI) as a basic dye and 200 g of pure water were added to a separable flask, and the mixture was stirred at 60 °C for 30 minutes. Then, an aqueous solution of Acid Red 52 (CI) as an acid dye, obtained by dissolving 11.50 g (0.019.8 mol) in 120 g of pure water was added, and the mixture was stirred at 60 °C for 60 minutes. Heating was then stopped, and the mixture was stirred and cooled to room temperature. After cooling to room temperature, the reaction solution was filtered to obtain a purple solid. This solid was dried under reduced pressure at 60 °C for 8 hours to obtain the salt-forming compound d-1.
[0337] <Preparation of salt-forming compound d-2>
[0338] Using the same method as d-1, and replacing CI Basic Blue 7 with CI Basic Blue 26 as a basic dye, salt-forming compound d-2 was obtained.
[0339] <Preparation of Pigment Dispersion 1>
[0340] To 742.39 g of PGMEA as a solvent, 15.00 g of S-20000, a pigment dispersant with basic groups, was added, followed by 2.70 g of a PGMEA solution containing 1.00 wt% 4-methylbenzenesulfonic acid. Next, the mixture was stirred for 1 hour at atmospheric pressure and 25°C, and then allowed to stand for 6 hours, thereby pre-forming a salt between the basic groups of S-20000 and the sulfonyl groups of 4-methylbenzenesulfonic acid. Then, 149.91 g of an alkali-soluble resin solution (a resin solution obtained by dissolving the above-mentioned PIP-1 in PGMEA to a solid content of 30 wt% (solid content 30.0 wt%)) was added, and the mixture was stirred for 30 minutes. Then, 90.00 g of a benzodifuranone-based black pigment with the structure shown below was mixed and stirred for 20 minutes to obtain a pre-dispersion. The pre-dispersion was then transferred to a container filled with 75 vol% of a dispersion medium. The pigment dispersion was performed once in a bead mill using zirconia beads (“Torayceram”, a registered trademark, manufactured by Toray Industries, Inc.), followed by wet media dispersion in a circulating manner. After 30 minutes, every 10 minutes of dispersion time, an appropriate amount was taken from the outlet of the disperser into a glass bottle container. The sampled pigment dispersion was placed in a laser diffraction and scattering particle size distribution measuring device (UPA150, manufactured by Microtrac Corporation) to measure the average dispersed particle size. The pigment dispersion with an average dispersed particle size of 150 ± 10 nm as the median particle size D50 (cumulative 50% volume average diameter) and an average particle size of 300 ± 30 nm as the median particle size D90 (cumulative 90% volume average diameter) was designated as “pigment dispersion 1”.
[0341] [Chemical Formula 16]
[0342]
[0343] <Preparation of Pigment Dispersion 2>
[0344] Using the same steps as for "pigment dispersion 1", PIP-1 was dissolved using MBA instead of PGMEA to prepare "pigment dispersion 2".
[0345] <Preparation of Pigment Dispersion 3>
[0346] 200g of zirconium nitride particles (ZrN, manufactured by NISSHINENGINEERING Co., Ltd.) produced using thermal plasma method, 50g of polyimide precursor resin (PIP-1), and 1000g of γ-butyrolactone (GBL) were loaded into a tank and stirred for 20 minutes using a homogenizer to obtain a pre-dispersion. The mixture was then added to a container filled with 75% by volume... The pre-dispersion solution supplied by the zirconia beads was dispersed at a speed of 10 m / s for 3 hours using a centrifugal separator (Ultra Apex Mill, manufactured by HIROSHIMA METAL & MACHINERY Co., Ltd.) to obtain a pigment dispersion 3 with a solid component concentration of 20% by weight and a colorant / resin (weight ratio) of 80 / 20. The composition is shown in Table 1.
[0347] [Table 1]
[0348] [Table 1]
[0349]
[0350] <Preparation of Pigment Dispersion 4>
[0351] Using the same method as pigment dispersion 3, the added alkali-soluble resin is PIP-2, thereby obtaining pigment dispersion 4.
[0352] <Preparation of Pigment Dispersion 5>
[0353] Using the same method as pigment dispersion 3, the added alkali-soluble resin is PIP-3, thereby obtaining pigment dispersion 5.
[0354] <Preparation of Pigment Dispersion 6>
[0355] Using the same method as pigment dispersion 3, the added alkali-soluble resin is PIP-4, thereby obtaining pigment dispersion 6.
[0356] <Preparation of Pigment Dispersion 7>
[0357] To 770.00 g of PGMEA as a solvent, 30.00 g of pigment dispersant 1 was added, and the mixture was stirred for 5 minutes. Then, 100.00 g of ZCR-1569H was added, and the mixture was stirred for 30 minutes. Next, as component (b), 100.00 g of SO100CF was added, and the mixture was stirred for 30 minutes to obtain a pre-stirred liquid. The pre-stirred liquid was then transferred to a container filled with [a specific substance] at a filling rate of 75% by volume. The material was subjected to a first wet media dispersion treatment for 3 hours in a vertical bead mill using a pulverizing media formed from composite oxides (zirconia: hafnium oxide: yttrium oxide: aluminum oxide = weight ratio 93.3:1.5:4.9:0.3, manufactured by Toray Industries, Inc.) in a circulating manner. The mixture was then fed into a container filled with [material name missing] at a 75% volume percentage. In a vertical bead mill using a pulverizing medium composed of composite oxides (zirconia: hafnium oxide: yttrium oxide: aluminum oxide = weight ratio 93.3:1.5:4.9:0.3, manufactured by Toray Industries, Inc.), a second wet media dispersion treatment was performed for 6 hours at a peripheral speed of 9 m / s using a circulating method. The mixture was then filtered using a 0.8 μm filter to prepare a pigment dispersion 1 with a solid component of 20.00 wt%. The proportions of each raw material are shown in Table 2.
[0358] [Table 2]
[0359]
[0360] <Preparation of photosensitive resin composition R-1>
[0361] Under a yellow light, in a solvent (C) containing γ-butyrolactone (GBL) and ethyl lactate (EL) in a 1:1 weight ratio, polyimide precursor resin PI-1 obtained in Synthesis Example 1 (A) as an alkali-soluble resin, compound b-1 obtained in Synthesis Example 10 (B) as a photosensitizer, compound d-1 (D) as a coloring material, which is a salt-forming compound formed from an acid dye and a basic dye, CI Solvent Blue 45 as a nonionic dye d-3, thermochromic compound f-1 (BIP-PHBZ) with the following structure, thermocrosslinking agent g-1 (HMOM-TPHAP) as other additives, compound h-1 (bisphenol AF) having a phenolic hydroxyl group, and adhesion modifier i-1 (KBM-403) were added and stirred until dissolved to prepare a positive photosensitive resin composition R-1.
[0362] [Chemical Formula 17]
[0363]
[0364] [Table 3]
[0365]
[0366] <Preparation of photosensitive resin compositions R-2 to R-6>
[0367] R-2 to R-6 were prepared in the same manner as R-1, using the compositions described in Table 3.
[0368] <Preparation of photosensitive resin composition R-7>
[0369] Under a yellow light, 0.20 g of NCI-831, used as a photosensitizer, was added to 13.01 g of PGMEA and stirred for 3 minutes to dissolve it. Then, 4.28 g of alkali-soluble polyimide resin solution A (a resin solution obtained by dissolving PI-1 in PGMEA with a solid content of 30% by weight) and 1.02 g of alkali-soluble Cardo resin solution A (amine value of 0 (mgKOH / g), resin acid value of 90 (mgKOH / g), solid content of 44.2% by weight, a PGMEA solution of alkali-soluble Cardo resin with carboxyl groups, namely "ADEKA ARKLS" (registered trademark) WR-301 (manufactured by ADEKA Corporation)) were added, along with 0.99 g of DPCA-60, a compound having two or more free radical polymerizable groups. The mixture was stirred to obtain a blended solution. The mixing solution was mixed with 10.50 g of pigment dispersion 1 sampled from the supernatant of the glass bottle container, and stirred for 30 minutes to obtain negative photosensitive resin composition R-7. The proportions of the raw materials are shown in Table 4.
[0370] [Table 4]
[0371]
[0372] <Preparation of Photosensitive Resin Composition R-8>
[0373] Alkali-soluble polyimide resin solution B (a resin solution obtained by dissolving PI-1 in MBA with a solid component of 30% by weight) was used instead of alkali-soluble polyimide resin solution A. Furthermore, pigment dispersion 2 was used instead of pigment dispersion 1. Using the same steps as R-7, negative photosensitive resin composition R-8 was prepared. The proportions of the raw materials are shown in Table 4.
[0374] <Synthetic Example 11: Synthesis of hydrophobic materials (e-1) and (e-2)>
[0375] 100 parts by weight of cyclohexanone were added to a 1000 mL reaction vessel equipped with a stirrer, reflux condenser, dropping funnel, thermometer, and nitrogen inlet. The mixture was heated to 110 °C under a nitrogen atmosphere. The temperature of the cyclohexanone was maintained at 110 °C, and the monomer mixture solutions shown in Table 5 were added dropwise at a constant rate over 2 hours using a dropping funnel to prepare the monomer solutions. After the addition was complete, the monomer solutions were heated to 115 °C and reacted for 2 hours to obtain liquephobic materials (e-1) and (e-2).
[0376] [Table 5]
[0377]
[0378] <Synthesis Example 12: Synthesis of Phenolic Resin (j-1)>
[0379] Under a dry nitrogen stream, 108.0 g (1.00 mol) of m-cresol, 75.5 g (0.93 mol) of 37% formaldehyde aqueous solution, 0.63 g (0.005 mol) of oxalic acid dihydrate, and 264 g of methyl isobutyl ketone were added and impregnated in an oil bath, allowing the reaction solution to reflux while undergoing a condensation reaction for 4 hours. Then, after 3 hours, the temperature of the oil bath was increased, and the pressure inside the flask was reduced to 4.0 kPa–6.7 kPa to remove volatile components. The dissolved resin was then cooled to room temperature to obtain Novolac type phenolic resin (j-1). According to GPC, the weight-average molecular weight is 3,500.
[0380] <Preparation of photosensitive resin compositions R-9 and R-10>
[0381] Under a yellow light, the components were mixed according to the proportions shown in Table 6 and stirred thoroughly at room temperature to dissolve them. Then, the resulting solution was filtered through a 1 μm pore size filter to obtain positive photosensitive resin compositions R-9 and R-10.
[0382] [Table 6]
[0383]
[0384] <Preparation of photosensitive resin composition R-11>
[0385] To 93.8 g of pigment dispersion 3, 50.5 g of alkali-soluble resin (PIP-1), 17.0 g of quinone diazide compound (b-1) as a photoacid generator, 13.6 g of phenolic compound (h-1, bisphenol AF), 0.2 g of organosilicon surfactant (BYK-333), 105.0 g of GBL, and 720.0 g of PGME were added to obtain a positive photosensitive resin composition R-11 with a total solid content concentration of 10% by weight and a pigment / resin (weight ratio) of 15 / 85. The composition is shown in Table 7.
[0386] [Table 7]
[0387]
[0388] <Preparation of photosensitive resin composition R-12>
[0389] Using the same method as R-11, pigment dispersion 3 was replaced with pigment dispersion 4 as the input pigment dispersion, and PIP-1 was replaced with PIP-2 as the alkali-soluble resin, to obtain positive photosensitive resin composition R-12. The composition is shown in Table 7.
[0390] <Preparation of photosensitive resin composition R-13>
[0391] Using the same method as R-11, pigment dispersion 3 was replaced with pigment dispersion 5 as the input pigment dispersion, and PIP-1 was replaced with PIP-3 as the alkali-soluble resin, to obtain positive photosensitive resin composition R-13. The composition is shown in Table 7.
[0392] <Preparation of photosensitive resin composition R-14>
[0393] Using the same method as R-11, pigment dispersion 3 was replaced with pigment dispersion 6 as the input pigment dispersion, and PIP-1 was replaced with PIP-4 as the alkali-soluble resin, to obtain positive photosensitive resin composition R-14. The composition is shown in Table 7.
[0394] <Preparation of photosensitive resin composition R-15>
[0395] Under yellow light, 10.0 g of polyimide precursor resin (PIP-1) as (A) an alkali-soluble resin, 1.2 g of f-1 as (B) a photosensitizer, and 32.0 g of PGME and 8.0 g of GBL as (C) organic solvents were added. Then, using... The obtained solution was filtered through a filter to obtain a positive photosensitive resin composition R-15.
[0396] <Preparation of photosensitive resin composition R-16>
[0397] Under yellow light, 0.38 g of OXE03 as a photopolymerization initiator was added to a mixed solvent of 8.50 g of MBA and 16.16 g of PGMEA, and stirred for 10 minutes to dissolve. Then, 1.88 g of MEK-ST-40 was added as a silica particle dispersion (component (a)), and stirred for 10 minutes to dissolve. Next, 4.61 g of ZAH-106, 0.45 g of TR4020G, 0.38 g of DPCA-60, and 0.97 g of GA-5060P were added, and stirred for 30 minutes to obtain a transparent blend. 16.69 g of pigment dispersion 7 was mixed into this blend, and stirred for 30 minutes to prepare a negative photosensitive resin composition R-16 with a solid content of 15.00% by weight. The proportions of each raw material are shown in Table 8.
[0398] [Table 8]
[0399]
[0400] <Preparation of photosensitive resin composition R-17>
[0401] Similar to the preparation of R-16, negative photosensitive resin composition R-17 was prepared by replacing MEK-ST-40 with OSCAL-1421 in the proportions shown in Table 8. The proportions of each raw material are shown in Table 8.
[0402] <Preparation of photosensitive resin composition R-18>
[0403] Similar to the preparation of R-16, MEK-ST-L was used instead of MEK-ST-40, and the negative photosensitive resin composition R-18 was prepared in the proportions shown in Table 8. The proportions of each raw material are shown in Table 8.
[0404] <Examples 1-25, Comparative Examples 1-3>
[0405] The surface roughness of the pixel segmentation layer and spacer, the diffused and reflected light of the substrate, the sealing performance of the organic EL display device, weather resistance reliability, electrical reliability, and luminous characteristics in each embodiment and comparative example are evaluated as follows.
[0406] First, in the center of a 100mm × 100mm PET substrate, AgPdCu (100nm) and crystalline ITO (10nm), serving as the first electrode, were sequentially deposited using vacuum sputtering, and etched into 100 strips with a linewidth of 60μm, a spacing of 100μm, and a length of 10mm. This resulted in an exposed portion of the substrate with a width of 40μm. Next, photosensitive resin compositions conforming to the embodiments and comparative examples shown in Table 9 were spin-coated, and then pre-baked on a heating plate at 100°C for 2 minutes to form a film.
[0407] After UV exposure of the film through the halftone photomask shown in Table 9, it was developed with a 2.38% TMAH aqueous solution. In negative development, only the unexposed portions were dissolved; in positive development, only the exposed portions were dissolved. The film was then rinsed with pure water to obtain the pattern. It was then cured in an oven at 250°C under a nitrogen atmosphere for 60 minutes to obtain a substrate with a patterned pixel segmentation layer and spacers. It should be noted that by adjusting the spin coating speed, the thickness of the pixel segmentation layer and the thickness of the spacers were 1.5 μm in all embodiments and comparative examples.
[0408] It should be noted that in Comparative Example 1, a photomask without a semi-transparent portion, commonly referred to as a full-tone mask, was used to fabricate the pixel segmentation layer and spacers separately. That is, after coating, pre-baking, exposure, development, and curing of the pixel segmentation layer, the spacers underwent coating, pre-baking, exposure, development, and curing processes. Furthermore, in Comparative Example 3, after curing, a plasma treatment apparatus (SPC-100B+H, manufactured by Hitachi High-Technologies) was used to perform a roughening treatment in RIE mode, with oxygen, 1000W, and for 60 seconds.
[0409] In this state, the surface roughness of the pixel segmentation layer and spacers and the diffused reflected light of the substrate were evaluated, and the results are shown in Table 10.
[0410] Next, an organic EL layer was formed over the entire surface of the patterned substrate using vacuum evaporation. It should be noted that the vacuum level during evaporation was set to 1×10⁻⁶. -3 Below Pa, during the evaporation process, the substrate is rotated relative to the evaporation source. First, as a hole injection layer, compound (HT-1) is deposited for 10 nm, and as a hole transport layer, compound (HT-2) is deposited for 50 nm. Next, as a light-emitting layer, compound (GH-1) as the host material and compound (GD-1) as the dopant material are deposited at a doping concentration of 10% by volume to a thickness of 40 nm. Next, as an electron transport layer, compound (ET-1) and LiQ are stacked at a volume ratio of 1:1 to a thickness of 40 nm. The hole injection layer, hole transport layer, light-emitting layer, and electron transport layer described above are referred to as the first light-emitting unit.
[0411] Then, 2 nm of LiQ was deposited as an electron injection layer. The structure of the compound used as the organic EL layer is shown below.
[0412] [Chemical Formula 18]
[0413]
[0414] [Chemical Formula 19]
[0415]
[0416] Then, Mg and Ag were deposited at a volume ratio of 10:1, with a thickness of 10 nm, intersecting with the first electrode, to form 20 strip-shaped second electrodes with a linewidth of 400 μm, a spacing of 500 μm, and a length of 10 mm. It should be noted that the film thickness referred to here is the value displayed by a quartz oscillating film thickness monitor.
[0417] In this way, an organic EL display device with 200 light-emitting elements having 100 first electrodes and 20 second electrodes intersecting each other was completed. A schematic diagram of the organic EL display device of this embodiment is shown below. Figure 8 A schematic diagram of a light-emitting element with the organic EL layer omitted is shown in Figure 9 Then, the sealing performance, weather resistance reliability, and electrical reliability of the organic EL display device were evaluated. The results are shown in Table 10.
[0418] [Table 9-1]
[0419]
[0420] [Table 9-2]
[0421]
[0422] [Table 10-1]
[0423]
[0424] [Table 10-2]
[0425]
[0426] [Table 11]
[0427]
[0428] <Example 26>
[0429] In the first light-emitting unit, only compound (ET-1) was used in the electron transport layer instead of LiQ. Otherwise, an organic EL display device was fabricated in the same manner as in Example 1, and the adhesion, weather resistance reliability, electrical reliability, and luminescence characteristics of the organic EL display device were evaluated. The conditions of the photosensitive resin composition and photomask are shown in Table 9, and the evaluation results are shown in Table 10.
[0430] <Example 27>
[0431] In the first light-emitting unit, only compound (ET-2) was used in the electron transport layer instead of LiQ. Otherwise, an organic EL display device was fabricated in the same manner as in Example 1, and the adhesion, weather resistance reliability, electrical reliability, and luminescence characteristics of the organic EL display device were evaluated. The conditions of the photosensitive resin composition and photomask are shown in Table 9, and the evaluation results are shown in Table 10.
[0432] <Example 28>
[0433] In the first light-emitting unit, LiQ was not used in the electron transport layer, but only compound (ET-3) was used. Otherwise, an organic EL display device was fabricated in the same manner as in Example 1, and the adhesion, weather resistance reliability, electrical reliability, and luminescence characteristics of the organic EL display device were evaluated. The conditions of the photosensitive resin composition and photomask are shown in Table 9, and the evaluation results are shown in Table 10.
[0434] <Example 29>
[0435] In the first light-emitting unit, LiQ was not used in the electron transport layer, but only compound (ET-4) was used. Otherwise, an organic EL display device was fabricated in the same manner as in Example 1, and the adhesion, weather resistance reliability, electrical reliability, and luminescence characteristics of the organic EL display device were evaluated. The conditions of the photosensitive resin composition and photomask are shown in Table 9, and the evaluation results are shown in Table 10.
[0436] <Example 30>
[0437] After obtaining a patterned substrate in the same manner as in Example 1, a first light-emitting unit is stacked as an organic EL layer. Then, on the first light-emitting unit, as an n-type charge generation layer, compound (ET-1) and metal Li as a dopant are deposited at a deposition rate ratio of compound (ET-1):Li = 99:1 for 10 nm. Next, as a p-type charge generation layer, compound (HT-1) is deposited for 10 nm.
[0438] Following the charge generation layer, an organic EL layer identical to the first light-emitting unit is formed again, thus creating a tandem configuration. Then, LiQ is deposited at a depth of 2 nm as an electron injection layer. Next, Mg and Ag are deposited at a volume ratio of 10:1 at a depth of 10 nm, intersecting with the first electrode, to form 20 strip-shaped second electrodes with a linewidth of 400 μm, a spacing of 500 μm, and a length of 10 mm. It should be noted that the film thickness referred to here is the value displayed by a quartz oscillating film thickness monitor.
[0439] In this manner, an organic EL display device with 200 light-emitting elements having 100 first electrodes and 20 second electrodes intersecting each other was completed. Then, the sealing performance, weather resistance reliability, electrical reliability, and luminescence characteristics of the organic EL display device were evaluated. The conditions of the photosensitive resin composition and photomask are shown in Table 9, and the evaluation results are shown in Table 10.
[0440] <Example 31>
[0441] Except that the compound (ET-1) in the n-type charge generation layer is changed to compound (ET-2), the organic EL display device was fabricated in the same manner as in Example 30, and the adhesion, weather resistance reliability, electrical reliability, and luminescence characteristics of the organic EL display device were evaluated. The conditions of the photosensitive resin composition and photomask are shown in Table 9, and the evaluation results are shown in Table 10.
[0442] <Example 32>
[0443] Except that the compound (ET-1) in the n-type charge generation layer is changed to compound (ET-3), the organic EL display device was fabricated in the same manner as in Example 30, and the adhesion, weather resistance reliability, electrical reliability, and luminescence characteristics of the organic EL display device were evaluated. The conditions of the photosensitive resin composition and photomask are shown in Table 9, and the evaluation results are shown in Table 10.
[0444] <Example 33>
[0445] Except that the compound (ET-1) in the n-type charge generation layer is changed to compound (ET-4), the organic EL display device was fabricated in the same manner as in Example 30, and the adhesion, weather resistance reliability, electrical reliability, and luminescence characteristics of the organic EL display device were evaluated. The conditions of the photosensitive resin composition and photomask are shown in Table 9, and the evaluation results are shown in Table 10.
[0446] Explanation of reference numerals in the attached figures
[0447] 1. Substrate
[0448] 2 First electrode
[0449] 3-pixel segmentation layer
[0450] 4 spacers
[0451] 5 Organic EL layer
[0452] 6 Second electrode
[0453] 7 TFT
[0454] 8. Planarization layer
[0455] 9. Sealing layer
[0456] 10 Polarizing layer
[0457] 11 Ultraviolet Absorption Layer
[0458] 12 Light-transmitting section
[0459] 13 Semi-transparent section
[0460] 14 shading part
[0461] 15 Cylinders
[0462] 16. Range of objects for Ra1 determination
[0463] 17. Range of objects for Ra2 determination
[0464] 18 Organic EL Display Device
[0465] 19. Light-emitting elements
Claims
1. An organic EL display device, comprising a substrate, an organic EL layer, and a second electrode, wherein the substrate has a first electrode, a pixel segmentation layer, and spacers on a substrate. When the maximum value of the surface roughness Ra1 of the pixel segmentation layer and the surface roughness Ra2 of the spacer is set as Ramax, Ramax is above 1.0 nm and below 50 nm, and the absolute value of the difference between Ra1 and Ra2 is above 1.0 nm.
2. The organic EL display device as claimed in claim 1, wherein, Ra1 becomes Ramax.
3. The organic EL display device as described in claim 2, wherein, Of the area of the interface between the substrate and the organic EL layer, the area of the interface between the pixel segmentation layer and the organic EL layer is more than 50%.
4. The organic EL display device as claimed in claim 1, wherein, Ra2 becomes Ramax.
5. The organic EL display device as claimed in claim 4, wherein, Of the area of the interface between the substrate and the organic EL layer, the area of the interface between the spacer and the organic EL layer is 50% or more.
6. The organic EL display device according to any one of claims 1 to 5, wherein, The pixel segmentation layer contains silicon dioxide particles with a primary particle size of 5–30 nm.
7. The organic EL display device according to any one of claims 1 to 5, wherein, The pixel segmentation layer comprises a cured film of a photosensitive resin composition containing an alkali-soluble resin.
8. The organic EL display device as claimed in claim 7, wherein, The alkali-soluble resin contains one or more selected from the group consisting of acrylic resin, phenolic resin, polysiloxane resin, Cardo resin, polyimide resin, polyimide precursor resin, polybenzoxazole resin, and polybenzoxazole precursor resin.
9. The organic EL display device as claimed in claim 7, wherein, The photosensitive resin composition contains a coloring material.
10. The organic EL display device as claimed in claim 7, wherein, The photosensitive resin composition contains a hydrophobic material.
11. The organic EL display device according to any one of claims 1 to 5, wherein, The organic EL layer includes an electron transport layer and / or a charge generation layer.
12. The organic EL display device as claimed in claim 11, wherein, The electron transport layer and / or charge generation layer contain donor dopants.
13. The organic EL display device as claimed in claim 12, wherein, The donor dopant contains one or more of the following: alkali metals, alkaline earth metals, rare earth metals; inorganic salts of the alkali metals, alkaline earth metals, rare earth metals; or complexes of the alkali metals, alkaline earth metals, rare earth metals, and organic compounds.
14. The organic EL display device as claimed in claim 11, wherein, The electron transport layer and / or charge generation layer comprises a compound having a phenanthroline skeleton represented by the following general formula (1). [Chemical Formula 1] Here, R1 to R8 can be the same or different, and can be selected from hydrogen atoms, alkyl groups, cycloalkyl groups, alkenyl groups, cycloalkenyl groups, aryl groups, heteroaryl groups, and heterocyclic groups; wherein at least one of R1, R3, R6, and R8 is selected from adamantyl, norbornel, phenyl vinyl, β-naphthyl, phenanthryl, and pyrene.
15. The organic EL display device as claimed in claim 11, wherein, The electron transport layer and / or charge generation layer comprises a compound having a phenanthroline skeleton represented by the following general formula (2). [Chemical Formula 2] Here, R9~R 16 Each can be the same or different, selected from hydrogen atom, alkyl group, cycloalkyl group, alkenyl group, cycloalkenyl group, aryl group, heteroaryl group, heterocyclic group, and X1; among which, R9 to R 16 At least one of them is X1; n represents a natural number from 2 to 6; X1 is a single bond, or an n-valent linking unit that connects multiple phenanthroline skeletons from any of benzene, anthracene, pyridine, ethylene, thiophene, furan, methylene, carbazole, cyclohexane, spirodifluorene, triphenylamine, triphenylene, and structures formed by combining them.
16. A method for manufacturing an organic EL display device, comprising a substrate, an organic EL layer, and a second electrode, wherein the substrate has a first electrode, a pixel segmentation layer, and spacers on a substrate. The manufacturing method includes a step of processing a pixel segmentation layer and a spacer together such that when the maximum value of the surface roughness Ra1 of the pixel segmentation layer and the surface roughness Ra2 of the spacer is set to Ramax, Ramax is 1.0 nm or more and 50 nm or less, and the absolute value of the difference between Ra1 and Ra2 is 1.0 nm or more. The photomask used for processing together is a halftone photomask having a light-transmitting part, a light-blocking part, and a semi-light-transmitting part.
17. The method of manufacturing an organic EL display device as claimed in claim 16, wherein, The transmittance of the semi-transparent portion is 15% to 50% of the transmittance of the transparent portion.
Citation Information
Patent Citations
Display panel and electronic device having display panel
JP2004281365A
Method for manufacturing toner for electrostatic charge image development
JP2018097251A
Organic light emitting diode device
JP2020087935A
Near-infrared transmitting black azo pigments
US20020121228A1
Black perylene pigments
WO2005078023A2
